Insecticide seed treatments for managing maggots (Diptera: Anthomyiidae) in onion across selected regions in North America - Leonardo D. Salgado; Alan G. Taylor; Mary Ruth McDonald; Rob G. Wilson; Timothy D. Waters; Josephine B. Antwi; Stuart Reitz; Nathan Hesler; Brian A. Nault (Crop Protection, 2026)

Examining widely held propositions on human dietary protein needs and benefits: a critical review of the science that shapes both the data and our understanding of an essential macronutrient - Mitchell M. Kanter; Sally Aaron; Steven N. Austad; Andrew W. Brown; Nicholas A. Burd; Wayne W. Campbell; Mark Cope; Teresa A. Davis; John W. Erdman; Miguel Freitas; Kristen Hicks-Roof; Samuel Klein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Validation of sanitizer efficacy in commercial apple dump tanks using a Listeria monocytogenes surrogate - Yuan Su; Mengqian Hang; Xiaoye Shen; Zi Hua; To Chiu; Jeanene M. Deavila; Qi Sun; Bhim B. Thapa; Edmund L. Afari; Yiqing Du; Stuart Goatley; Manoella Mendoza; et al. (Food Microbiology, 2026)

Towards standardized molecular monitoring of HABs: A consensus guide to qPCR - Uwe John; Dave Clarke; Holly Bowers; Shauna Murray; Antonella Penna; Amna Ashfaq; Karl Blyth Andree; Mathiroopini Andipalagan; Elisa Berdalet; Silvia Casabianca; Catarina Churro; Anette Engesmo; et al. (Harmful Algae, 2026)

Integrated geological, economic, and risk assessment of underground hydrogen storage - Prakash Purswani; K C Bijay; Hyeonseok Lee; Yun Yang; Uwaila C. Iyare; Lawrence O. Baompong; Shaowen Mao; David Z. Li; Zhidi Wu; Manjeet Chhetri; Siqin Yu; Xiaoyu Zhang; et al. (Fuel, 2026)

Comparing loss-on-ignition, acid decarbonation and combustion elemental analysis for measuring organic carbon concentrations – recommendations for best practice - Robert B. Sparkes; Stuart A. Rae; Lucy McMahon; Hannah L. Mossman; David McKendry; Clare E. Dean; Graham Tinsley; Frances Fowden; Connor J. Grisdale; Hafiza Begum; Holly Hope; Charlotte McEnhill; et al. (Organic Geochemistry, 2026)

Development of emission factors for pollutants from dominant fuelwood species in Northern South Africa - Khuthadzo Manyatsha; Burgert B Hattingh; Stuart Piketh; Frederik H Conradie; Joshua Edokpayi (Air Quality, Atmosphere & Health, 2026)
Residential biomass combustion in rural communities is recognised as a major contributor to air pollution, representing the second-largest source of gaseous emissions and the primary source of atmospheric particulate matter. In many African countries, including South Africa, residential emission inventories and air quality assessments rely largely on international emission factors (EFs), introducing considerable uncertainty due to regional differences in fuel characteristics, combustion technologies, and household energy-use practices. Generating locally derived EFs is therefore essential for improving the accuracy of emission inventories and supporting effective air quality management and climate policy development. This study quantified the EFs of CO₂, CO, NO, SO₂, and PM₁₀ from the combustion of the 12 predominantly preferred fuelwood species used for household energy in rural Limpopo Province, South Africa. Controlled combustion experiments were conducted using a traditional three-legged cookstove in a simulated village kitchen under laboratory conditions. The mean EFs determined for CO₂, CO, NO, SO₂, and PM₁₀ were 1389 ± 149, 131.38 ± 91.4, 1.22 ± 0.63, 5.16 ± 4.9, and 64.7 ± 76.3 g kg⁻¹, respectively. Modified combustion efficiency (MCE) exhibited a statistically significant negative association with the EFs of CO and SO₂, indicating that lower combustion efficiency was associated with higher emissions of these pollutants. In contrast, fuel moisture content was not significantly associated with the EFs of CO₂, NO, or PM₁₀, while no statistically significant relationship was observed between fuel nitrogen (N) content and NO EFs. Furthermore, no statistically significant differences were detected among the investigated fuelwood species in the individual EFs of CO₂, CO, NO, SO₂, and PM₁₀. This study provides the first laboratory-derived, species-specific EF dataset for the predominantly preferred fuelwood species used in rural Limpopo Province. The findings reduce uncertainties associated with the application of international default EFs and provide a robust basis for improving residential biomass emission inventories, air quality modelling, and the development of evidence-based air pollution mitigation and climate management strategies in South Africa and other regions with similar household energy-use patterns.

Validation of SPH code Spheral to model interacting solid bodies in a supersonic flow - Veronika A. Korneyeva; Jason M. Pearl; Kathryn M. Kumamoto; J. Michael Owen; Cody D. Raskin; Megan B. Syal; Nicholaus J. Parziale; Stuart J. Laurence (Icarus, 2026)

The future of evolutionary behavioral biology - Theo C. M. Bakker; James F. A. Traniello; Tim R. Birkhead; Monika Borgerhoff Mulder; Bernard Crespi; Niels J. Dingemanse; Raghavendra Gadagkar; Ashleigh S. Griffin; Mark E. Hauber; Bert Hölldobler; John L. Hoogland; Sarah B. Hrdy; et al. (Behavioral Ecology and Sociobiology, 2026)

From kelp forests to turf reefs: Patterns, drivers, and impacts to functional diversity - Shane P. Farrell; Dara S. Yiu; Stuart K. Ryan; Rene D. Francolini; Courtney E. Stuart; Jonathan S. Lefcheck; Yasmina M. Shah Esmaeili; Douglas B. Rasher (Ecology, 2026)
Kelp forests are declining in many regions due to ocean warming, predator loss, and other anthropogenic stressors. In areas of rapid ocean warming, including the southern Gulf of Maine, these ecosystems have transitioned to a novel state dominated by low‐lying mats of turf algae. However, the pace, drivers, and ecological consequences of this transition remain unclear. Here, we used field surveys from 32 sites over 5 years (2018–2023) to reveal a continuation of kelp forest collapse and northward expansion of turf algae across Maine's coast. Next, we united data on benthic cover with key environmental variables in a structural equation model to show that turf algae were directly enhanced by higher ocean temperatures and decreased wave disturbance and indirectly enhanced by a warming‐induced loss of kelp cover. Lastly, we revealed the shift from kelp to turf yielded a seaweed assemblage dominated by traits associated with rapid growth, high surface area‐to‐volume ratios, and markedly reduced canopy height, indicating declines in habitat provisioning and carbon storage with kelp forest loss. Our findings highlight the accelerating impacts of climate change on temperate reef ecosystems and the vital services they provide. Further, we provide insights into a new state shift that is now occurring globally and underscore the need for urgent actions to mitigate further loss of foundational kelp forests.

Effects of duration of a plant-based diet stimulus at first feeding on nutritional programming in Atlantic salmon (Salmo salar) - Xu Gong; Matthew Sprague; Stuart McMillan; Pedro Gómez-Requeni; Fernando Norambuena; Sam A. M. Martin; Douglas R. Tocher; Mónica B. Betancor (Fish Physiology and Biochemistry, 2026)
Nutritional programming could potentially be a strategy for sustainable aquaculture to adapt fish to feeds formulated with low levels of marine ingredients. The present study examined the effects of early dietary stimulus duration and the impacts of a later challenge with a similar diet. At first feeding, Atlantic salmon ( Salmo salar ) fry of ~ 0.15 g initial weight were fed a vegetable diet (77% plant-based ingredients) for either 1 (V1) or 2 weeks (V2), while a control group (M) received a marine diet (86% marine-based ingredients) for the 2 weeks (stimulus phase). All fish then received a marine diet for 16 weeks (intermediate phase) before being refed a vegetable diet for 6 weeks (challenge phase). Water temperature was 13 °C during the trial, and the only difference between the three experimental groups (V1, V2 and M) was their dietary regime during the first 2 weeks. Obviously, stimulus duration had no phenotypic impacts on growth or tissue fatty acid compositions of either total or polar lipids after challenge. However, the expressions of key genes of LC-PUFA biosynthesis were upregulated significantly in the V1 group, whereas the expressions of most transcription factors were downregulated in the V2 group. After the challenge, the circular muscle thickness of the intestine in the V1 group was increased by 15%, and goblet cell numbers were reduced by 15%. Overall, further investigations about the duration of the stimulus and assessment with longer challenges are required to elicit positive effects and to refine the use of nutritional programming in Atlantic salmon.

Hybrid particulate matter generated by lava-ignited wildfires at the Litli-Hrútur 2023 eruption, Iceland - Laura Wainman; Evgenia Ilyinskaya; Melissa Anne Pfeffer; Penny E. Wieser; David Damby; James B. McQuaid; Celine Mandon; Enikö Bali; Josefa Sepulveda-Araya; Richard Walshaw; Caleb Hall; Stuart Micklethwaite; et al. (Science of The Total Environment, 2026)

Agricultural nitrous oxide emissions across twenty years of micrometeorological observations show trends associated with soil freezing and fertilizer application - Leah Brown; Ian B. Strachan; David E. Pelster; Stuart Admiral; Luc Pelletier; Brian Grant; Ward Smith; Elizabeth Pattey (Science of The Total Environment, 2026)

Monitoring CO2 mineralisation and dissolution at CarbFix2 using inherent isotopes of CO2, H2O and noble gases - C.M. Holdsworth; B. Chen; L. Tamraz; S.Ó. Snæbjörnsdóttir; M.J. Voigt; B. Sigfússon; G. Johnson; F.M. Stuart; A.J. Boyce; R.S. Haszeldine; S.M.V. Gilfillan (International Journal of Greenhouse Gas Control, 2026)

Changing volatile emissions and sources along the Ethiopian Rift - Abate A. Melaku; Gemechu B. Teferi; Takele Mihretie; Snorri Gudbrandsson; Yared Sinetebeb; Peter H. Barry; Tobias P. Fischer; Finlay M. Stuart; Ugur Balci; Sæmundur A. Halldórsson; Chris J. Ballentine; Darren J. Hillegonds; et al. (Earth and Planetary Science Letters, 2026)

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Mapping area of habitat for inland wetland species - Francesca A. Ridley; Catherine A. Sayer; Louise Mair; Daniele Baisero; Monika Böhm; Thomas M. Brooks; Stuart H. M. Butchart; Viola Clausnitzer; Jeorg Freyhof; Günther Grill; Ian Harrison; Randall R. Jiménez; et al. (Conservation Biology, 2026)
Area of habitat (AOH) maps provide a high‐resolution representation of the habitat available in a species’ range and can support conservation policy and planning processes. However, until recently, there was insufficient knowledge on the distribution of inland wetlands and freshwater biodiversity to develop AOH mapping methods specifically tailored to inland wetlands. We used a combined empirical and thematic approach to translate inland wetland habitat classes in the International Union for Conservation of Nature (IUCN) Habitats Classification Scheme into spatially explicit wetland‐cover types derived from the Global Lakes and Wetlands Database 2 and the World Karst Aquifer Map. The AOH was subsequently estimated as the area in the mapped range that corresponded to each species’ habitat and elevation associations. We developed and tested the method with IUCN Red List assessment data, range maps, and point locality data for fishes, odonates, decapod crustaceans, and mollusks (22,876 species). The method performed well in comparison with similar methods already developed for terrestrial mammals, birds, amphibians, and reptiles. The mean map prevalence (proportion of area in a species’ range that was AOH) was 18–32% for each taxonomic group. Based on data on known localities of occurrence, 78–100% of species per taxonomic group had a higher classification accuracy than expected if AOH were distributed in the range at random. This represents an increased accuracy in the distribution of wetland species. Our study represents the first attempt to distinguish between inland wetland habitat subclasses and to include subterranean habitats in an AOH mapping method. Our method will facilitate the inclusion of previously underrepresented taxa in key conservation tools and analyses and is expected to increase the accuracy of AOH mapping for any species associated with inland wetlands.

The Dynamic Roles of Repressor Element 1-Silencing Transcription Factor (REST): A Double-Edged Sword in Neural Health and Disease - Taslima Akter Eva; Avinash Shenoy; Veer B. Gupta; Viswanthram Palanivel; Akanksha Salkar; Sohrab Nowroozi Nasab; Nitin Chitranshi; Mehdi Mirzaei; Yuyi You; Stuart L. Graham; Devaraj Basavarajappa; Vivek Gupta (Molecular Neurobiology, 2026)

Hindsight informs foresight: revisiting millennial forecasts of impacts and status of rocky shores in 2025 - Stephen J. Hawkins; Kathryn A. O'Shaughnessy; George M. Branch; Laura Airoldi; Simon Bray; Paul Brooks; Michael T. Burrows; Juan Carlos Castilla; Tasman P. Crowe; Thomas W. Davies; Louise B. Firth; Keith Hiscock; et al. (Marine Pollution Bulletin, 2025)

Climate-driven trans-Tasman population increase of the habitat-modifying, range extending sea urchin Centrostephanus rodgersii - Sterling B. Tebbett; Graham J. Edgar; Celia A. Balemi; John P. Keane; Nick T. Shears; Arie J.P. Spyksma; Rick D. Stuart-Smith; Scott D. Ling (Journal of Environmental Management, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Modelling and mapping of subsurface nitrate-attenuation index in agricultural landscapes - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne (Journal of Environmental Management, 2025)

Per- and polyfluoroalkyl substances (PFAS) mass flux and mass balance at an aqueous film-forming foam release site in semiarid eastern New Mexico, USA - Erin L. Gray; Samuel E. Potteiger; Trevor D. Brannon; Stuart B. Norton; Jay Cho; Michael D. Annable (Journal of Contaminant Hydrology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Latitudinal gradients in herbivorous and detritivorous reef fish productivity - Sterling B. Tebbett; Helen F. Yan; Scott Bennett; Graham J. Edgar; Scott D. Ling; Rick D. Stuart-Smith; David R. Bellwood (Reviews in Fish Biology and Fisheries, 2025)

International Consortium to Classify Ageing-related Pathologies (ICCARP) senescence definitions: achieving international consensus - Emma Short; Robert T. R. Huckstepp; Kambiz Alavian; Winfried M. K. Amoaku; Thomas M. Barber; Edwin J. R. van Beek; Emyr Benbow; Sunil Bhandari; Phillip Bloom; Carlo Cota; Paul Chazot; Gary Christopher; et al. (GeroScience, 2025)

Interactions between nutritional programming, genotype, and gut microbiota in Atlantic salmon: Long-term effects on gut microbiota, fish growth and feed efficiency - Simona Rimoldi; Karla Fernandez Quiroz; Violeta Kalemi; Stuart McMillan; Ingunn Stubhaug; Laura Martinez-Rubio; Mónica B. Betancor; Genciana Terova (Aquaculture, 2025)

Fire resilience analysis: Using high temporal and spatial satellite imagery for rehabilitated landscapes - Phillip B. McKenna; Stuart Phinn; Peter D. Erskine (Ecological Engineering, 2025)

Evaluating the effectiveness of seabird bycatch mitigation measures for pelagic longlines in the South Atlantic - James B. Bell; Johannes H. Fischer; Ana P.B. Carneiro; Shane Griffiths; Alessandra Bielli; Sebastián Jiménez; Steffen Oppel; Richard A. Phillips; Helen M. Wade; Oliver Yates; Stuart A. Reeves (Biological Conservation, 2025)

EuPPollNet : A European Database of Plant‐Pollinator Networks - Jose B. Lanuza; Tiffany M. Knight; Nerea Montes‐Perez; Will Glenny; Paola Acuña; Matthias Albrecht; Maddi Artamendi; Isabelle Badenhausser; Joanne M. Bennett; Paolo Biella; Ricardo Bommarco; Andree Cappellari; et al. (Global Ecology and Biogeography, 2025)
Motivation Pollinators play a crucial role in maintaining Earth's terrestrial biodiversity. However, rapid human‐induced environmental changes are compromising the long‐term persistence of plant‐pollinator interactions. Unfortunately, we lack robust, generalisable data capturing how plant‐pollinator communities are structured across space and time. Here, we present the EuPPollNet (European Plant‐Pollinator Networks) database, a fully open European‐level database containing harmonised taxonomic data on plant‐pollinator interactions referenced in both space and time, along with other ecological variables of interest. In addition, we evaluate the taxonomic and sampling coverage of EuPPollNet, and summarise key structural properties in plant‐pollinator networks. We believe EuPPollNet will stimulate research to address data gaps in plant‐pollinator interactions and guide future efforts in conservation planning. Main Types of Variables Included EuPPollNet contains 1,162,109 interactions between plants and pollinators from 1864 distinct networks, which belong to 52 different studies distributed across 23 European countries. Information about sampling methodology, habitat type, biogeographic region and additional taxonomic rank information (i.e. order, family, genus and species) is also provided. Spatial Location and Grain The database contains 1214 different sampling locations from 13 different natural and anthropogenic habitats that fall in 7 different biogeographic regions. All records are geo‐referenced and presented in the World Geodetic System 1984 (WGS84). Time Period and Grain Species interaction data was collected between 2004 and 2021. Major Taxa and Level of Measurement The database contains interaction data at the species level for 94% of the records, including a total of 1411 plant and 2223 pollinator species. The database includes data on 6% of the European species of flowering plants, 34% of bees, 26% of butterflies and 33% of syrphid species at the European level. Software Format The database was built with R and is stored in ‘.rds’ and ‘.csv’ formats. Its construction is fully reproducible and can be accessed at: https://doi.org/10.5281/zenodo.14747448 .

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Adverse impacts of off-road vehicles on coastal dune vegetation are widespread, substantial, and long-lasting: Evidence from a global meta-analysis of sandy beach-dune systems - Thomas A. Schlacher; Michael A. Weston; Shane Orchard; Brendan P. Kelaher; Brooke Maslo; Jenifer E. Dugan; David M. Hubbard; Leonardo Costa; Melanie J. Bishop; Kristal N. Kostoglu; Ben L. Gilby; Christofer J. Henderson; et al. (Estuarine, Coastal and Shelf Science, 2025)

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

Assessment of spatial variability and temporal stability of groundwater redox conditions in New Zealand - Stephen B. Collins; Ranvir Singh; Stuart R. Mead; David J. Horne; Jon K. F. Roygard (Environmental Monitoring and Assessment, 2024)

Widespread upper-ocean deoxygenation in the Alpine-Mediterranean Tethys during the Toarcian Oceanic Anoxic Event - Wenhan Chen; David B. Kemp; Hugh C. Jenkyns; Stuart A. Robinson; Shouyi Jiang; Chengrong Pan; Chao Li (Global and Planetary Change, 2024)

Vegetation recovery of rehabilitated pasture at three coal mine sites following fire disturbance - Phillip B. McKenna; David Doley; Natasha Ufer; Vanessa Glenn; Stuart Phinn; Peter D. Erskine (Ecological Engineering, 2024)

Hydrological connectivity and environment characteristics explain spatial variation in fish assemblages in a wet–dry tropical river - Kaitlyn O’Mara; Michael Venarsky; Ben Stewart-Koster; Glenn B. McGregor; Cameron Schulz; Jonathan Marshall; Stuart E. Bunn (Hydrobiologia, 2024)
Hydrological connectivity in river systems facilitates the movement of animals across riverine landscapes and influences fish habitat but is threatened by climate change and water resource developments. We studied fish assemblages across a large wet–dry tropical river system in northern Australia that is under consideration for new agricultural and water resource developments, which are expected to alter hydrological connectivity. We explored relationships between the environment and several biotic variables; fish taxonomic composition, species turnover, and species trait presence, quantifying how they were related to hydrological connectivity. Environmental dissimilarity of sites was influenced by hydrological connectivity variables, including flow, elevation, and river distance. Environment characteristics and hydrological connectivity together were important predictors of fish taxonomic composition. Fish species turnover was highest in headwater sites, and species presence absence was related to feeding and reproductive traits. Our results suggest that habitat specialists and species with reproductive traits that depend on hydrological connectivity, such as diadromous species, are most vulnerable to declines in relative abundance following a reduction in connectivity, which would lead to range contractions within catchments. Maintaining habitats that support taxonomically and functionally unique fish assemblages, such as wetlands and headwater streams, is important for maintaining biodiversity.

Evaluating rational and healthy use options for small pelagic fish species in sub-Saharan Africa - Stuart W. Bunting; Djiga Thiao; Molly Ahern; Yaw B. Ansah; Ansen Ward; Joshua Wesana; Rodrigue Yossa; Lena Westlund (Food Security, 2024)

The many ages of Triton: New crater counts on the Voyager high-resolution image sequence and implications for impactor provenance - William B. McKinnon; Kelsi N. Singer; Stuart J. Robbins; Michelle R. Kirchoff; Simon B. Porter; Paul M. Schenk; Ted Stryk; Jeffrey M. Moore (Icarus, 2024)

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2024) - Peter Simmonds; Evelien M. Adriaenssens; Elliot J. Lefkowitz; Hanna M. Oksanen; Stuart G. Siddell; Francisco Murilo Zerbini; Poliane Alfenas-Zerbini; Frank O. Aylward; Donald M. Dempsey; Bas E. Dutilh; Juliana Freitas-Astúa; María Laura García; et al. (Archives of Virology, 2024)
This article reports changes to virus taxonomy and taxon nomenclature that were approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2024. The entire ICTV membership was invited to vote on 203 taxonomic proposals that had been approved by the ICTV Executive Committee (EC) in July 2023 at the 55th EC meeting in Jena, Germany, or in the second EC vote in November 2023. All proposals were ratified by online vote. Taxonomic additions include one new phylum ( Ambiviricota ), one new class, nine new orders, three new suborders, 51 new families, 18 new subfamilies, 820 new genera, and 3547 new species (excluding taxa that have been abolished). Proposals to complete the process of species name replacement to the binomial (genus + species epithet) format were ratified. Currently, a total of 14,690 virus species have been established.

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Intracerebral Administration of a Novel Self-Assembling Peptide Hydrogel Is Safe and Supports Cell Proliferation in Experimental Intracerebral Haemorrhage - Faye Bolan; Ben R. Dickie; James R. Cook; Josephine M. Thomas; Emmanuel Pinteaux; Stuart M. Allan; Alberto Saiani; Catherine B. Lawrence (Translational Stroke Research, 2024)
Intracerebral haemorrhage (ICH) is the deadliest form of stroke, but current treatment options are limited, meaning ICH survivors are often left with life-changing disabilities. The significant unmet clinical need and socioeconomic burden of ICH mean novel regenerative medicine approaches are gaining interest. To facilitate the regeneration of the ICH lesion, injectable biomimetic hydrogels are proposed as both scaffolds for endogenous repair and delivery platforms for pro-regenerative therapies. In this paper, the objective was to explore whether injection of a novel self-assembling peptide hydrogel (SAPH) Alpha2 was feasible, safe and could stimulate brain tissue regeneration, in a collagenase-induced ICH model in rats. Alpha2 was administered intracerebrally at 7 days post ICH and functional outcome measures, histological markers of damage and repair and RNA-sequencing were investigated for up to 8 weeks. The hydrogel Alpha2 was safe, well-tolerated and was retained in the lesion for several weeks, where it allowed infiltration of host cells. The hydrogel had a largely neutral effect on functional outcomes and expression of angiogenic and neurogenic markers but led to increased numbers of proliferating cells. RNAseq and pathway analysis showed that ICH altered genes related to inflammatory and phagocytic pathways, and these changes were also observed after administration of hydrogel. Overall, the results show that the novel hydrogel was safe when injected intracerebrally and had no negative effects on functional outcomes but increased cell proliferation. To elicit a regenerative effect, future studies could use a functionalised hydrogel or combine it with an adjunct therapy.

The Impact of Land Conversion on Primate Habitats: Refining the Extent of Occurrence Data for Four Capuchin Species in North and Northeastern Brazil - Anailda T. Farias; Stuart E. Hamilton; Luciana B. M. Pires; Gustavo R. Canale; Ricardo R. Santos; Andrea Presotto (International Journal of Primatology, 2024)
Conversion of primate forest habitat is a global concern with significant implications for primate populations. Although the geospatial Extent of Occurrence (EOO) data provided for primates by the International Union for the Conservation of Nature are widely used, they do not accurately reflect the existing extent of primate species because of ongoing habitat loss. We focused on four capuchin monkey species ( Sapajus apella , S. flavius , S, libidinosus , and S. xanthosternos ), all native to North and Northeastern Brazil, to prioritize research by the Capuchin Action Network. We refined the EOOs for the four primate species using MapBiomas land cover data. We accounted for areas of agriculture, urban, and mining and updated the EOOs of the four species. Additionally, we evaluated the Conservation Units in each EOO. Conservation Units are protected areas critical to mitigating habitat loss in Brazil. Our results show that S. apella has lost the smallest amount of its EOO (13%), while S. flavius has lost the most (77%). Agriculture was the leading cause of land cover change, followed by urbanization and mining. We provide an updated EOO for the four capuchin species and highlight the need for conservation efforts to address the challenges posed by human activities in the capuchin species’ habitats.

Comparison of three reanalysis‐driven regional climate models over New Zealand: Climatology and extreme events - Isaac Campbell; Peter B. Gibson; Stephen Stuart; Ashley M. Broadbent; Abha Sood; Amir A. S. Pirooz; Neelesh Rampal (International Journal of Climatology, 2024)
Three ~12‐km reanalysis‐driven regional climate models (RCMs) are evaluated in terms of capturing climatologies and extremes of precipitation, temperature and surface wind over Aotearoa/New Zealand (NZ). NZ provides an excellent case study for evaluating high‐resolution RCMs due to its coastal and complex terrain and isolated geographical position in the midlatitudes, exposed to both tropical and polar influences. Overall, we find that the RCMs faithfully reproduce the observed climate, with precipitation and temperature climatologies particularly well‐captured. However, the RCMs display significant differences from observations in capturing the surface wind climatology, highlighting a remaining key challenge. The excess “drizzle problem” is apparent to varying degrees, leading to a weaker representation in the length of meteorological drought in some regions. The RCMs also diverge in reproducing diurnal temperature range which appears partly related to cloud cover. Finally, we discuss the important role of observational uncertainty in the context of model evaluation.

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

X-ray translucent reaction cell for simulation of carbon mineral storage reservoir environments - Ian D. Watt; Ian B. Butler; James Gilgannon; Lucas Martins; Florian Fusseis; R. Stuart Haszeldine; Ian Molnar; Stuart M.V. Gilfillan (International Journal of Greenhouse Gas Control, 2024)

Methane fluxes in tidal marshes of the conterminous United States - Ariane Arias‐Ortiz; Jaxine Wolfe; Scott D. Bridgham; Sara Knox; Gavin McNicol; Brian A. Needelman; Julie Shahan; Ellen J. Stuart‐Haëntjens; Lisamarie Windham‐Myers; Patty Y. Oikawa; Dennis D. Baldocchi; Joshua S. Caplan; et al. (Global Change Biology, 2024)
Methane (CH 4 ) is a potent greenhouse gas (GHG) with atmospheric concentrations that have nearly tripled since pre‐industrial times. Wetlands account for a large share of global CH 4 emissions, yet the magnitude and factors controlling CH 4 fluxes in tidal wetlands remain uncertain. We synthesized CH 4 flux data from 100 chamber and 9 eddy covariance (EC) sites across tidal marshes in the conterminous United States to assess controlling factors and improve predictions of CH 4 emissions. This effort included creating an open‐source database of chamber‐based GHG fluxes ( https://doi.org/10.25573/serc.14227085 ). Annual fluxes across chamber and EC sites averaged 26 ± 53 g CH 4 m −2 year −1 , with a median of 3.9 g CH 4 m −2 year −1 , and only 25% of sites exceeding 18 g CH 4 m −2 year −1 . The highest fluxes were observed at fresh‐oligohaline sites with daily maximum temperature normals (MATmax) above 25.6°C. These were followed by frequently inundated low and mid‐fresh‐oligohaline marshes with MATmax ≤25.6°C, and mesohaline sites with MATmax >19°C. Quantile regressions of paired chamber CH 4 flux and porewater biogeochemistry revealed that the 90th percentile of fluxes fell below 5 ± 3 nmol m −2 s −1 at sulfate concentrations >4.7 ± 0.6 mM, porewater salinity >21 ± 2 psu, or surface water salinity >15 ± 3 psu. Across sites, salinity was the dominant predictor of annual CH 4 fluxes, while within sites, temperature, gross primary productivity (GPP), and tidal height controlled variability at diel and seasonal scales. At the diel scale, GPP preceded temperature in importance for predicting CH 4 flux changes, while the opposite was observed at the seasonal scale. Water levels influenced the timing and pathway of diel CH 4 fluxes, with pulsed releases of stored CH 4 at low to rising tide. This study provides data and methods to improve tidal marsh CH 4 emission estimates, support blue carbon assessments, and refine national and global GHG inventories.

Lead-up and manifestation of the Oceanic Anoxic Event 2 at the DSDP Site 398 (Vigo Seamount, NW Iberian offshore): Palynological and geochemical insights - Iván Rodríguez-Barreiro; Artai A. Santos; Uxue Villanueva-Amadoz; Stephen Louwye; Stuart A. Robinson; José B. Diez (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Riverine concentrations and export of dissolved silicon, and potential controls on nutrient stoichiometry, across the land–ocean continuum in Great Britain - Andrew M. Tye; Helen P. Jarvie; Bryan M. Spears; Nancy B. Dise; Jennifer L. Williamson; Dan J. Lapworth; Don Monteith; Richard Sanders; Daniel J. Mayor; Michael J. Bowes; Michael Bowes; Annette Burden; et al. (Journal of Hydrology, 2024)

Dynamical downscaling CMIP6 models over New Zealand: added value of climatology and extremes - Peter B. Gibson; Stephen Stuart; Abha Sood; Dáithí Stone; Neelesh Rampal; Hamish Lewis; Ashley Broadbent; Marcus Thatcher; Olaf Morgenstern (Climate Dynamics, 2024)
Dynamical downscaling provides physics-based high-resolution climate change projections across regional and local scales. This is particularly important for island nations characterized by complex terrain, where the coarse resolution of global climate model (GCM) output often prohibits direct use. One of the main motivations for dynamical downscaling is to reduce biases relative to the host GCM at the local scale, which can be quantified through assessing ‘added value’. However, added value from downscaling is not guaranteed; quantifying this can help users make informed decisions about how best to use available climate projection data. Here we describe the experiment design of the updated national climate projections for New Zealand based on dynamical downscaling. The global non-hydrostatic Conformal Cubic Atmospheric Model (CCAM) is primarily used for downscaling, with a global stretched grid targeting high resolution over New Zealand (12-km) and the wider South Pacific region (12–35-km). Focusing on the historical simulations, we assess added value for a range of metrics, climatological fields, extreme indices, and tropical cyclones. The main strengths of the downscaling include generally large improvements relative to the host GCM for temperature and orographic precipitation. Inter-annual variability in temperature is well captured across New Zealand, and several temperature and precipitation-based extreme indices show large improvements. The representation of tropical cyclones reaching at least category 2 intensity is generally improved relative to the large consistent under-representation in the host GCMs. The remaining biases are explored and discussed forming the basis for ongoing bias-correction work.

Juvenile survival increases with dispersal distance and varies across years: 15 years of evidence in a prairie perennial - Lea K. Richardson; Scott W. Nordstrom; Amy Waananen; Riley D. Thoen; Amy B. Dykstra; Gretel Kiefer; Drake E. Mullett; Erin G. Eichenberger; Ruth G. Shaw; Stuart Wagenius (Ecology, 2024)
Juvenile survival is critical to population persistence and evolutionary change. However, the survival of juvenile plants from emergence to reproductive maturity is rarely quantified. This is especially true for long‐lived perennials with extended pre‐reproductive periods. Furthermore, studies rarely have the replication necessary to account for variation among populations and cohorts. We estimated juvenile survival and its relationship to population size, density of conspecifics, distance to the maternal plant, age, year, and cohort for Echinacea angustifolia , a long‐lived herbaceous perennial. In 14 remnant prairie populations over seven sampling years, 2007–2013, we identified 886 seedlings. We then monitored these individuals annually until 2021 (8–15 years). Overall, juvenile mortality was very high; for almost all cohorts fewer than 10% of seedlings survived to age 8 or to year 2021. Only two of the seedlings reached reproductive maturity within the study period. Juvenile survival increased with distance from the maternal plant and varied more among the study years than it did by age or cohort. Juvenile survival did not vary with population size or local density of conspecific neighbors. Our results suggest that low juvenile survival could contribute to projected population declines.

Can nutritional programming in Atlantic salmon (Salmo salar) be optimised with a reduced stimulus period? - Stuart McMillan; Samuel A.M. Martin; Elżbieta Król; Fernando Norambuena; Simon Baumgärtner; Xu Gong; Marwa Mamdouh Tawfik; Brett Glencross; John F. Taylor; Douglas R. Tocher; Mónica B. Betancor (Aquaculture, 2024)

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Rapid determination of site-specific N, P, and K management for rice in a tidal swampland - Setia Sari Girsang; Alexander M. Stuart; Budi Raharjo; Pauline Chivenge; Niluh Putu S. Ratmini; Hasil Sembiring; Yustisia; Agus Suprihatin; Irish Lorraine B. Pabuayon; Roland J. Buresh (Nutrient Cycling in Agroecosystems, 2024)

Aligning theoretical and empirical representations of soil carbon-to-nitrogen stoichiometry with process-based terrestrial biogeochemistry models - Katherine S. Rocci; Cory C. Cleveland; Brooke A. Eastman; Katerina Georgiou; A. Stuart Grandy; Melannie D. Hartman; Emma Hauser; Hannah Holland-Moritz; Emily Kyker-Snowman; Derek Pierson; Peter B. Reich; Else P. Schlerman; et al. (Soil Biology and Biochemistry, 2024)

Closing the gap between existing large‐area imaging research and marine conservation needs - Orion S. McCarthy; Kanisha Contractor; Will F. Figueira; Arthur C. R. Gleason; T. Shay Viehman; Clinton B. Edwards; Stuart A. Sandin (Conservation Biology, 2024)
Emerging technology has immense potential to increase the scale and efficiency of marine conservation. One such technology is large‐area imaging (LAI), which relies on structure‐from‐motion photogrammetry to create composite products, including 3‐dimensional (3‐D) environmental models, that are larger in spatial extent than the individual images used to create them. Use of LAI has become widespread in certain fields of marine science, primarily to measure the 3D structure of benthic ecosystems and track change over time. However, the use of LAI in the field of marine conservation appears limited. We conducted a review of the coral reef literature on the use of LAI to identify research themes and regional trends in applications of this technology. We also surveyed 135 coral reef scientists and conservation practitioners to determine community familiarity with LAI, evaluate barriers practitioners face in using LAI, and identify applications of LAI believed to be most exciting or relevant to coral conservation. Adoption of LAI was limited primarily to researchers at institutions based in advanced economies and was applied infrequently to conservation, although conservation practitioners and survey respondents from emerging economies indicated they expect to use LAI in the future. Our results revealed disconnect between current LAI research topics and conservation priorities identified by practitioners, highlighting the need for more diverse, conservation‐relevant research using LAI. We provide recommendations for how early adopters of LAI (typically Global North scientists from well‐resourced institutions) can facilitate access to this conservation technology. These recommendations include developing training resources, creating partnerships for data storage and analysis, publishing standard operating procedures for LAI workflows, standardizing methods, developing tools for efficient data extraction from LAI products, and conducting conservation‐relevant research using LAI.

Reasons to Be Skeptical about Sentience and Pain in Fishes and Aquatic Invertebrates - Benjamin K. Diggles; Robert Arlinghaus; Howard I. Browman; Steven J. Cooke; Robin L. Cooper; Ian G. Cowx; Charles D. Derby; Stuart W. Derbyshire; Paul JB Hart; Brian Jones; Alexander O. Kasumyan; Brian Key; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Top ten priorities for global saltmarsh restoration, conservation and ecosystem service research - Julien Pétillon; Emma McKinley; Meghan Alexander; Janine B. Adams; Christine Angelini; Thorsten Balke; John N. Griffin; Tjeerd Bouma; Sally Hacker; Qiang He; Marc J.S. Hensel; Carles Ibáñez; et al. (Science of The Total Environment, 2023)

Correction to: Changes to virus taxonomy and the ICTV Statutes ratifed by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Understanding Osmolality: A Manufacturer’s Methodology and Clinical Considerations for Enteral Nutrition - B. Cassady; S. Hertzler; E. Stuart; L. Fledderjohann (Journal of the Academy of Nutrition and Dietetics, 2023)

Mid-season adjustment of nitrogen fertilizer for rice with two plant spacings - Setia S. Girsang; Alexander M. Stuart; Dorkas Parhusip; Erpina D. Manurung; Miswarti; Irish Lorraine B. Pabuayon; Roland J. Buresh (Field Crops Research, 2023)

Life in the fast lane: Revisiting the fast growth—High survival paradigm during the early life stages of fishes - Dominique Robert; Jun Shoji; Pascal Sirois; Akinori Takasuka; Ignacio A. Catalán; Arild Folkvord; Stuart A. Ludsin; Myron A. Peck; Su Sponaugle; Patricia M. Ayón; Richard D. Brodeur; Emily Y. Campbell; et al. (Fish and Fisheries, 2023)
Early life survival is critical to successful replenishment of fish populations, and hypotheses developed under the Growth‐Survival Paradigm (GSP) have guided investigations of controlling processes. The GSP postulates that recruitment depends on growth and mortality rates during early life stages, as well as their duration, after which the mortality declines substantially. The GSP predicts a shift in the frequency distribution of growth histories with age towards faster growth rates relative to the initial population because slow‐growing individuals are subject to high mortality (via starvation and predation). However, mortality data compiled from 387 cases published in 153 studies (1971–2022) showed that the GSP was only supported in 56% of cases. Selection against slow growth occurred in two‐thirds of field studies, leaving a non‐negligible fraction of cases showing either an absence of or inverse growth‐selective survival, suggesting the growth‐survival relationship is more complex than currently considered within the GSP framework. Stochastic simulations allowed us to assess the influence of key intrinsic and extrinsic factors on the characteristics of surviving larvae and identify knowledge gaps on the drivers of variability in growth‐selective survival. We suggest caution when interpreting patterns of growth selection because changes in variance and autocorrelation of individual growth rates among cohorts can invalidate fundamental GSP assumptions. We argue that breakthroughs in recruitment research require a comprehensive, population‐specific characterization of the role of predation and intrinsic factors in driving variability in the distribution and autocorrelation of larval growth rates, and of the life stage corresponding to the endpoint of pre‐recruited life.

Experimental evaluation of the use of embedded fiber Bragg gratings to measure steady and unsteady flow-induced marine propeller blade deformation - Antoine Ducoin; Ramona B. Barber; Stuart J. Wildy; John D. Codrington; Aaron Baker (Ocean Engineering, 2023)

Variability in composition of parrotfish bite scars across space and over time on a central Pacific atoll - Jonathan A. Charendoff; Clinton B. Edwards; Nicole E. Pedersen; Vid Petrovic; Brian Zgliczynski; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2023)
Parrotfishes are conspicuous herbivores, microvores, and detritivores in coral reef ecosystems, and the impacts of their feeding, particularly their capacity to expose reef carbonate, have received much attention. In many cases, parrotfish assemblages have been shown to control algal proliferation and promote the settlement of corals and crustose coralline algae (CCA). In extreme cases, high densities of parrotfishes may negatively affect net reef accretion through bioerosion and targeted coral predation. Most evidence describing the impacts of parrotfish foraging on benthic community structure is based upon correlations between benthic composition and parrotfish behavior or abundance, with much less known about process-based change of individual parrotfish bite scars through time. Here, we estimated parrotfish bite selectivity and determined the change in benthic composition within parrotfish bite scars relative to change in the overall reefscape using data collected over a 12-month duration from the fore reef habitat at Palmyra Atoll. We identified 2150 parrotfish bite scars which appeared most frequently on turf algae covered substrata but also on coral, CCA, and encrusting macroalgae. Of those bites taken on live coral, 96% of scars returned to live coral within 12 months. Notably, adult coral survivorship in bite scars was higher than at randomly sampled coral-covered locations not affected by parrotfish bites. The exposed substrate within bite scars was most commonly colonized by the dominant benthic functional group in the area immediately surrounding the scar. We found little evidence of coral recruitment to bite scars (1/2150); however, CCA growth on bites initially on turf algae increased from 18.4 to 32.9% across the two time intervals. Our results suggest that benthic areas affected by parrotfish bites were more likely to undergo a successional shift to a more calcified state relative to unaffected benthic areas, indicating that parrotfish grazing helps maintain highly calcified coral reef ecosystems.

KRILLPODYM: a mechanistic, spatially resolved model of Antarctic krill distribution and abundance - David B. Green; Olivier Titaud; Sophie Bestley; Stuart P. Corney; Mark A. Hindell; Rowan Trebilco; Anna Conchon; Patrick Lehodey (Frontiers in Marine Science, 2023)
Robust prediction of population responses to changing environments requires the integration of factors controlling population dynamics with processes affecting distribution. This is true everywhere but especially in polar pelagic environments. Biological cycles for many polar species are synchronised to extreme seasonality, while their distributions may be influenced by both the prevailing oceanic circulation and sea-ice distribution. Antarctic krill (krill, Euphausia superba ) is one such species exhibiting a complex life history that is finely tuned to the extreme seasonality of the Southern Ocean. Dependencies on the timing of optimal seasonal conditions have led to concerns over the effects of future climate on krill’s population status, particularly given the species’ important role within Southern Ocean ecosystems. Under a changing climate, established correlations between environment and species may breakdown. Developing the capacity for predicting krill responses to climate change therefore requires methods that can explicitly consider the interplay between life history, biological conditions, and transport. The Spatial Ecosystem And Population Dynamics Model (SEAPODYM) is one such framework that integrates population and general circulation modelling to simulate the spatial dynamics of key organisms. Here, we describe a modification to SEAPODYM, creating a novel model – KRILLPODYM – that generates spatially resolved estimates of krill biomass and demographics. This new model consists of three major components: (1) an age-structured population consisting of five key life stages, each with multiple age classes, which undergo age-dependent growth and mortality, (2) six key habitats that mediate the production of larvae and life stage survival, and (3) spatial dynamics driven by both the underlying circulation of ocean currents and advection of sea-ice. We present the first results of KRILLPODYM, using published deterministic functions of population processes and habitat suitability rules. Initialising from a non-informative uniform density across the Southern Ocean our model independently develops a circumpolar population distribution of krill that approximates observations. The model framework lends itself to applied experiments aimed at resolving key population parameters, life-stage specific habitat requirements, and dominant transport regimes, ultimately informing sustainable fishery management.

Changes to virus taxonomy and the ICTV Statutes ratified by the International Committee on Taxonomy of Viruses (2023) - Francisco Murilo Zerbini; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas‑Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2023)

Large effective population size masks population genetic structure in Hirondellea amphipods within the deepest marine ecosystem, the Mariana Trench - Stuart B. Piertney; Marius Wenzel; Alan J. Jamieson (Molecular Ecology, 2023)
The examination of genetic structure in the deep‐ocean hadal zone has focused on divergence between tectonic trenches to understand how environment and geography may drive species divergence and promote endemism. There has been little attempt to examine localized genetic structure within trenches, partly because of logistical challenges associated with sampling at an appropriate scale, and the large effective population sizes of species that can be sampled adequately may mask underlying genetic structure. Here we examine genetic structure in the superabundant amphipod Hirondellea gigas in the Mariana Trench at depths of 8126–10,545 m. RAD sequencing was used to identify 3182 loci containing 43,408 single nucleotide polymorphisms (SNPs) across individuals after stringent pruning of loci to prevent paralogous multicopy genomic regions being erroneously merged. Principal components analysis of SNP genotypes resolved no genetic structure between sampling locations, consistent with a signature of panmixia. However, discriminant analysis of principal components identified divergence between all sites driven by 301 outlier SNPs in 169 loci and significantly associated with latitude and depth. Functional annotation of loci identified differences between singleton loci used in analysis and paralogous loci pruned from the data set and also between outlier and nonoutlier loci, all consistent with hypotheses explaining the role of transposable elements driving genome dynamics. This study challenges the traditional perspective that highly abundant amphipods within a trench form a single panmictic population. We discuss the findings in relation to eco‐evolutionary and ontogenetic processes operating in the deep sea, and highlight key challenges associated with population genetic analysis in nonmodel systems with inherent large effective population sizes and genomes.

Inter-colony and inter-annual variation in discard use by albatross chicks revealed using isotopes and regurgitates - Amanda Kuepfer; Paulo Catry; Stuart Bearhop; Richard B. Sherley; Olivia Bell; Jason Newton; Paul Brickle; Alexander Arkhipkin; Stephen C. Votier (Marine Biology, 2023)
Effective marine ecosystem monitoring is critical for sustainable management. Monitoring seabird diets can convey important information on ecosystem health and seabird–fishery interactions. The diet of breeding black-browed albatross ( Thalassarche melanophris ) has previously been assessed using stomach content analysis (SCA) or stable isotope analysis (SIA), but not both methods together. Combining dietary sampling approaches reduces biases associated with using single methods. This study combines SCA and SIA to study the diet of black-browed albatross chicks, with a specific focus on fishery discard consumption, at two Falkland Islands colonies (New Island 51°43′S, 61°18′W and Steeple Jason Island 51°01′S, 61°13′W) during two consecutive breeding seasons (2019 and 2020). SCA provided high taxonomic resolution of short-term diet and priors for stable isotope mixing models, with multiple measures of dietary items (e.g. numeric frequency N%, frequency of occurrence FO%). By contrast, SIA of down feathers provided a single and more integrated dietary signal from throughout chick development. Although the two methods disagreed on the dominant prey group (SCA—crustacean; SIA—pelagic fish), the complementary information suggested a chick diet dominated by natural prey (SCA: 74%–93% [FO], 44%–98% [N]; SIA: minimum 87%–95% contribution). Nonetheless, SCA revealed that a high proportion of breeding adults do take discards. We detected consistent colony-specific diets in relation to prey species, but not in relation to higher discard use. Overall, discard consumption was highest in 2020, the year characterised by the poorest foraging conditions. Our results have implications for fisheries management and future dietary studies assessing discard use.

Analysis of the critical components of flash drought using the standardized evaporative stress ratio - Stuart G. Edris; Jeffrey B. Basara; Jordan I. Christian; Eric D. Hunt; Jason A. Otkin; Scott T. Salesky; Bradley G. Illston (Agricultural and Forest Meteorology, 2023)

Impact of bacterial strain acquisition in the lung of patients with COPD: the AERIS study - Lucio Malvisi; Aparna Yarraguntla; Marie-Cécile Mortier; Karen Osman; David W. Cleary; Béatrice Sente; Thierry G. Pascal; Vincent Weynants; Stuart C. Clarke; Laura Taddei; Tom M. A. Wilkinson; Jeanne-Marie Devaster; et al. (Infectious Diseases, 2022)

Recent changes to virus taxonomy ratified by the International Committee on Taxonomy of Viruses (2022) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Donald M. Dempsey; Bas E. Dutilh; María Laura García; R. Curtis Hendrickson; Sandra Junglen; Mart Krupovic; et al. (Archives of Virology, 2022)

Benthic assemblages are more predictable than fish assemblages at an island scale - Stuart A. Sandin; Esmeralda Alcantar; Randy Clark; Ramón de León; Faisal Dilrosun; Clinton B. Edwards; Andrew J. Estep; Yoan Eynaud; Beverly J. French; Michael D. Fox; Dave Grenda; Scott L. Hamilton; et al. (Coral Reefs, 2022)
Decades of research have revealed relationships between the abundance of coral reef taxa and local conditions, especially at small scales. However, a rigorous test of covariation requires a robust dataset collected across wide environmental or experimental gradients. Here, we surveyed spatial variability in the densities of major coral reef functional groups at 122 sites along a 70 km expanse of the leeward, forereef habitat of Curaçao in the southern Caribbean. These data were used to test the degree to which spatial variability in community composition could be predicted based on assumed functional relationships and site-specific anthropogenic, physical, and ecological conditions. In general, models revealed less power to describe the spatial variability of fish biomass than cover of reef builders (R 2 of best-fit models: 0.25 [fish] and 0.64 [reef builders]). The variability in total benthic cover of reef builders was best described by physical (wave exposure and reef relief) and ecological (turf algal height and coral recruit density) predictors. No metric of anthropogenic pressure was related to spatial variation in reef builder cover. In contrast, total fish biomass showed a consistent (albeit weak) association with anthropogenic predictors (fishing and diving pressure). As is typical of most environmental gradients, the spatial patterns of both fish biomass density and reef builder cover were spatially autocorrelated. Residuals from the best-fit model for fish biomass retained a signature of spatial autocorrelation while the best-fit model for reef builder cover removed spatial autocorrelation, thus reinforcing our finding that environmental predictors were better able to describe the spatial variability of reef builders than that of fish biomass. As we seek to understand spatial variability of coral reef communities at the scale of most management units (i.e., at kilometer- to island-scales), distinct and scale-dependent perspectives will be needed when considering different functional groups.

Giant Tree Frog diversification in West and Central Africa: Isolation by physical barriers, climate, and reproductive traits - Kyle E. Jaynes; Edward A. Myers; Václav Gvoždík; David C. Blackburn; Daniel M. Portik; Eli Greenbaum; Gregory F. M. Jongsma; Mark‐Oliver Rödel; Gabriel Badjedjea; Abraham Bamba‐Kaya; Ninda L. Baptista; Jeannot B. Akuboy; et al. (Molecular Ecology, 2022)
Secondary sympatry amongst sister lineages is strongly associated with genetic and ecological divergence. This pattern suggests that for closely related species to coexist in secondary sympatry, they must accumulate differences in traits that mediate ecological and/or reproductive isolation. Here, we characterized inter‐ and intraspecific divergence in three giant tree frog species whose distributions stretch across West and Central Africa. Using genome‐wide single‐nucleotide polymorphism data, we demonstrated that species‐level divergence coincides temporally and geographically with a period of large‐scale forest fragmentation during the late Pliocene. Our environmental niche models further supported a dynamic history of climatic suitability and stability, and indicated that all three species occupy distinct environmental niches. We found modest morphological differentiation amongst the species with significant divergence in tympanum diameter and male advertisement call. In addition, we confirmed that two species occur in secondary sympatry in Central Africa but found no evidence of hybridization. These patterns support the hypothesis that cycles of genetic exchange and isolation across West and Central Africa have contributed to globally significant biodiversity. Furthermore, divergence in both ecology and reproductive traits appear to have played important roles in maintaining distinct lineages. At the intraspecific level, we found that climatic refugia, precipitation gradients, marine incursions, and potentially riverine barriers generated phylogeographic structure throughout the Pleistocene and into the Holocene. Further studies examining phenotypic divergence and secondary contact amongst these geographically structured populations may demonstrate how smaller scale and more recent biogeographic barriers contribute to regional diversification.

Post-settlement demographics of reef building corals suggest prolonged recruitment bottlenecks - Lauranne Sarribouette; Nicole E. Pedersen; Clinton B. Edwards; Stuart A. Sandin (Oecologia, 2022)
For many organisms, early life stages experience significantly higher rates of mortality relative to adults. However, tracking early life stage individuals through time in natural settings is difficult, limiting our understanding of the duration of these ‘mortality bottlenecks’, and the time required for survivorship to match that of adults. Here, we track a cohort of juvenile corals (1–5 cm maximum diameter) from 12 taxa at a remote atoll in the Central Pacific from 2013 to 2017 and describe patterns of annual survivorship. Of the 537 juveniles initially detected, 219 (41%) were alive 4 years later, 163 (30%) died via complete loss of live tissue from the skeleton, and the remaining 155 (29%) died via dislodgement. The differing mortality patterns suggest that habitat characteristics, as well as species-specific features, may influence early life stage survival. Across most taxa, survival fit a logistic model, reaching > 90% annual survival within 4 years. These data suggest that mortality bottlenecks characteristic of ‘recruitment’ extend up to 5 years after individuals can be visually detected. Ultimately, replenishment of adult coral populations via sexual reproduction is needed to maintain both coral cover and genetic diversity. This study provides key insights into the dynamics and time scales that characterize these critical early life stages.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Genetic recruitment patterns are patchy and spatiotemporally unpredictable in a deep-water snapper (Lutjanus vivanus) sampled in fished and protected areas of western Puerto Rico - Stuart C. Willis; Christopher M. Hollenbeck; Jonathan B. Puritz; David S. Portnoy (Conservation Genetics, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Historical museum samples enable the examination of divergent and parallel evolution during invasion - Katarina C. Stuart; William B. Sherwin; Jeremy J. Austin; Melissa Bateson; Marcel Eens; Matthew C. Brandley; Lee A. Rollins (Molecular Ecology, 2022)
During the Anthropocene, Earth has experienced unprecedented habitat loss, native species decline and global climate change. Concurrently, greater globalization is facilitating species movement, increasing the likelihood of alien species establishment and propagation. There is a great need to understand what influences a species’ ability to persist or perish within a new or changing environment. Examining genes that may be associated with a species’ invasion success or persistence informs invasive species management, assists with native species preservation and sheds light on important evolutionary mechanisms that occur in novel environments. This approach can be aided by coupling spatial and temporal investigations of evolutionary processes. Here we use the common starling, Sturnus vulgaris , to identify parallel and divergent evolutionary change between contemporary native and invasive range samples and their common ancestral population. To do this, we use reduced‐representation sequencing of native samples collected recently in northwestern Europe and invasive samples from Australia, together with museum specimens sampled in the UK during the mid‐19th century. We found evidence of parallel selection on both continents, possibly resulting from common global selective forces such as exposure to pollutants. We also identified divergent selection in these populations, which might be related to adaptive changes in response to the novel environment encountered in the introduced Australian range. Interestingly, signatures of selection are equally as common within both invasive and native range contemporary samples. Our results demonstrate the value of including historical samples in genetic studies of invasion and highlight the ongoing and occasionally parallel role of adaptation in both native and invasive ranges.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Joint effects of climate, tree size, and year on annual tree growth derived from tree‐ring records of ten globally distributed forests - Kristina J. Anderson‐Teixeira; Valentine Herrmann; Christine R. Rollinson; Bianca Gonzalez; Erika B. Gonzalez‐Akre; Neil Pederson; M. Ross Alexander; Craig D. Allen; Raquel Alfaro‐Sánchez; Tala Awada; Jennifer L. Baltzer; Patrick J. Baker; et al. (Global Change Biology, 2022)
Tree rings provide an invaluable long‐term record for understanding how climate and other drivers shape tree growth and forest productivity. However, conventional tree‐ring analysis methods were not designed to simultaneously test effects of climate, tree size, and other drivers on individual growth. This has limited the potential to test ecologically relevant hypotheses on tree growth sensitivity to environmental drivers and their interactions with tree size. Here, we develop and apply a new method to simultaneously model nonlinear effects of primary climate drivers, reconstructed tree diameter at breast height (DBH), and calendar year in generalized least squares models that account for the temporal autocorrelation inherent to each individual tree's growth. We analyze data from 3811 trees representing 40 species at 10 globally distributed sites, showing that precipitation, temperature, DBH, and calendar year have additively, and often interactively, influenced annual growth over the past 120 years. Growth responses were predominantly positive to precipitation (usually over ≥3‐month seasonal windows) and negative to temperature (usually maximum temperature, over ≤3‐month seasonal windows), with concave‐down responses in 63% of relationships. Climate sensitivity commonly varied with DBH (45% of cases tested), with larger trees usually more sensitive. Trends in ring width at small DBH were linked to the light environment under which trees established, but basal area or biomass increments consistently reached maxima at intermediate DBH. Accounting for climate and DBH, growth rate declined over time for 92% of species in secondary or disturbed stands, whereas growth trends were mixed in older forests. These trends were largely attributable to stand dynamics as cohorts and stands age, which remain challenging to disentangle from global change drivers. By providing a parsimonious approach for characterizing multiple interacting drivers of tree growth, our method reveals a more complete picture of the factors influencing growth than has previously been possible.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Data challenges for future plant gene editing: expert opinion - Rim Lassoued; Diego M. Macall; Stuart J. Smyth; Peter W. B. Phillips; Hayley Hesseln (Transgenic Research, 2021)
Agricultural data in its multiple forms are ubiquitous. With progress in crop and input monitoring systems and price reductions over the past decade, data are now being captured at an unprecedented rate. Once compiled, organized and analyzed, these data are capable of providing valuable insights into much of the agri-food supply chain. While much of the focus is on precision farming, agricultural data applications coupled with gene editing tools hold the potential to enhance crop performance and global food security. Yet, digitization of agriculture is a double-edged sword as it comes with inherent security and privacy quandaries. Infrastructure, policies, and practices to better harness the value of data are still lacking. This article reports expert opinions about the potential challenges regarding the use of data relevant to the development and approval of new crop traits as well as mechanisms employed to manage and protect data. While data could be of great value, issues of intellectual property and accessibility surround many of its forms. The key finding of this research is that surveyed experts optimistically report that by 2030, the synergy of computing power and genome editing could have profound effects on the global agri-food system, but that the European Union may not participate fully in this transformation.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Characterization of clinical Ralstonia strains and their taxonomic position - Ad C. Fluit; Jumamurat R. Bayjanov; María Díez Aguilar; Rafael Cantón; Michael M. Tunney; J. Stuart Elborn; Mireille van Westreenen; Miquel B. Ekkelenkamp (Antonie van Leeuwenhoek, 2021)
To improve understanding of the role of Ralstonia in cystic fibrosis (CF), whole genomes of 18 strains from clinical samples were sequenced using Illumina technology. Sequences were analysed by core genome Multi-Locus Sequence Typing, Average Nucleotide Identity based on BLAST (ANIb), RAST annotation, and by ResFinder. Phylogenetic analysis was performed for the 16S rRNA gene, and the OXA-22 and OXA-60 ß-lactamase families. The minimal inhibitory concentrations (MICs) were determined using broth microdilution. ANIb data for the 18 isolates and 54 strains from GenBank, supported by phylogenetic analysis, showed that 8 groups of clusters (A-H), as well as subgroups that should be considered as species or subspecies. Groups A-C contain strains previously identified as Ralstonia solanacearum and Ralstonia pseudosolanacearum . We propose that group A is a novel species. Group B and C are Ralstonia syzygii , Ralstonia solanacearum , respectively. Group D is composed of Ralstonia mannitolilytica and Group E of Ralstonia pickettii . Group F and G should be considered novel species. Group H strains belong to R. insidiosa . OXA-22 and OXA-60 family ß-lactamases were encoded by all strains. Co-trimoxazole generally showed high activity with low MICs (≤1 mg/l) as did ciprofloxacin (≤0.12 mg/l). MICs against the other antibiotics were more variable, but generally high. RAST annotation revealed limited differences between the strains, and virulence factors were not identified. The taxonomy of the genus Ralstonia is in need of revision, but sequencing additional isolates is needed. Antibiotic resistance levels are high. Annotation did not identify potential virulence factors.

Limited Progress in Improving Gender and Geographic Representation in Coral Reef Science - Gabby N. Ahmadia; Samantha H. Cheng; Dominic A. Andradi-Brown; Stacy K. Baez; Megan D. Barnes; Nathan J. Bennett; Stuart J. Campbell; Emily S. Darling; Estradivari; David Gill; Erika Gress; Georgina G. Gurney; et al. (Frontiers in Marine Science, 2021)
Despite increasing recognition of the need for more diverse and equitable representation in the sciences, it is unclear whether measurable progress has been made. Here, we examine trends in authorship in coral reef science from 1,677 articles published over the past 16 years (2003–2018) and find that while representation of authors that are women (from 18 to 33%) and from non-OECD nations (from 4 to 13%) have increased over time, progress is slow in achieving more equitable representation. For example, at the current rate, it would take over two decades for female representation to reach 50%. Given that there are more coral reef non-OECD countries, at the current rate, truly equitable representation of non-OECD countries would take even longer. OECD nations also continue to dominate authorship contributions in coral reef science (89%), in research conducted in both OECD (63%) and non-OECD nations (68%). We identify systemic issues that remain prevalent in coral reef science (i.e., parachute science, gender bias) that likely contribute to observed trends. We provide recommendations to address systemic biases in research to foster a more inclusive global science community. Adoption of these recommendations will lead to more creative, innovative, and impactful scientific approaches urgently needed for coral reefs and contribute to environmental justice efforts.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

Typologies of collaborative governance for scaling nature-based solutions in two strategic South African river systems - Stephanie J. E. Midgley; Karen J. Esler; Petra B. Holden; Alanna J. Rebelo; Sabine I. Stuart-Hill; James D. S. Cullis; Nadine Methner (Ambio, 2021)

Fires slow population declines of a long-lived prairie plant through multiple vital rates - Scott W. Nordstrom; Amy B. Dykstra; Stuart Wagenius (Oecologia, 2021)

Long-term serological follow-up after primary Coxiella burnetii infection in patients with vascular risk factors for chronic Q fever - Sheila B. Buijs; Sanne K. Stuart; Jan Jelrik Oosterheert; Steffi Karhof; Andy I. M. Hoepelman; Nicole H. M. Renders; André S. van Petersen; Chantal P. Bleeker-Rovers; Peter C. Wever; Olivier H. J. Koning (European Journal of Clinical Microbiology & Infectious Diseases, 2021)
We evaluated the long-term serological follow-up of patients with vascular risk factors for chronic Q fever that were previously C oxiella burnetii seropositive. C. burnetii phase I IgG titers were reevaluated in patients that gave informed consent or retrospectively collected in patients already deceased or lost to follow-up. Of 107 patients, 25 (23.4%) became seronegative, 77 (72.0%) retained a profile of past resolved Q fever infection, and five (4.7%) developed chronic Q fever. We urge clinicians to stay vigilant for chronic Q fever beyond two years after primary infection and perform serological testing based on clinical presentation.

Characterization of basal forebrain glutamate neurons suggests a role in control of arousal and avoidance behavior - James T. McKenna; Chun Yang; Thomas Bellio; Marissa B. Anderson-Chernishof; Mackenzie C. Gamble; Abigail Hulverson; John G. McCoy; Stuart Winston; Erik Hodges; Fumi Katsuki; James M. McNally; Radhika Basheer; et al. (Brain Structure and Function, 2021)

Quantifying dispersal variability among nearshore marine populations - Katrina A. Catalano; Allison G. Dedrick; Michelle R. Stuart; Jonathan B. Puritz; Humberto R. Montes; Malin L. Pinsky (Molecular Ecology, 2021)
Dispersal drives diverse processes from population persistence to community dynamics. However, the amount of temporal variation in dispersal and its consequences for metapopulation dynamics is largely unknown for organisms with environmentally driven dispersal (e.g., many marine larvae, arthropods and plant seeds). Here, we used genetic parentage analysis to detect larval dispersal events in a common coral reef fish, Amphiprion clarkii , along 30 km of coastline consisting of 19 reef patches in Ormoc Bay, Leyte, Philippines. We quantified variation in the dispersal kernel across seven years (2012–2018) and monsoon seasons with 71 parentage assignments from 791 recruits and 1,729 adults. Connectivity patterns differed significantly among years and seasons in the scale and shape but not in the direction of dispersal. This interannual variation in dispersal kernels introduced positive temporal covariance among dispersal routes that theory predicts is likely to reduce stochastic metapopulation growth rates below the growth rates expected from only a single or a time‐averaged connectivity estimate. The extent of variation in mean dispersal distance observed here among years is comparable in magnitude to the differences across reef fish species. Considering dispersal variation will be an important avenue for further metapopulation and metacommunity research across diverse taxa.

Signatures of selection in a recent invasion reveal adaptive divergence in a highly vagile invasive species - Katarina C. Stuart; Adam P. A. Cardilini; Phillip Cassey; Mark F. Richardson; William B. Sherwin; Lee A. Rollins; Craig D. H. Sherman (Molecular Ecology, 2021)
A detailed understanding of population genetics in invasive populations helps us to identify drivers of successful alien introductions. Here, we investigate putative signals of selection in Australian populations of invasive common starlings, Sturnus vulgaris , and seek to understand how these have been influenced by introduction history. We used reduced representation sequencing to determine population structure, and identify Single Nucleotide Polymorphisms (SNPs) that are putatively under selection. We found that since their introduction into Australia, starling populations have become genetically differentiated despite the potential for high levels of dispersal, and that starlings have responded to selective pressures imposed by a wide range of environmental conditions across their geographic range. Isolation by distance appears to have played a strong role in determining genetic substructure across the starling's Australian range. Analyses of candidate SNPs that are putatively under selection indicated that aridity, precipitation and temperature may be important factors driving adaptive variation across the starling's invasive range in Australia. However, we also noted that the historic introduction regime may leave footprints on sites flagged as being under adaptive selection, and encourage critical interpretation of selection analyses in non‐native populations.

Scavenging amphipods from the Wallaby-Zenith Fracture Zone: Extending the hadal paradigm beyond subduction trenches - Johanna N. J. Weston; Rachael A. Peart; Heather A. Stewart; Heather Ritchie; Stuart B. Piertney; Thomas D. Linley; Alan J. Jamieson (Marine Biology, 2021)
Our understanding of the ecology of the hadal zone (> 6000 m depth) is based solely on subduction trenches, leaving other geomorphological features, such as fracture zones, troughs, and basins, understudied. To address this knowledge gap, the Wallaby-Zenith Fracture Zone, Indian Ocean (WZFZ; ~ 22°S, 102°E; maximum depth 6625 m measured during Expedition SO258) was studied using free-fall baited landers. We assessed the amphipod distribution and community assemblage of this non-subduction hadal feature and compared it to subduction hadal features. Eleven species were identified across the abyssal-hadal transition zone using a paired morphological and DNA barcoding approach. The community composition was found to change gradually from abyssal to hadal depths, which contrasts with the ecotone shift characteristic of subduction trenches. A large population of Bathycallisoma schellenbergi (Birstein & Vinogradov, 1958), a quintessential hadal amphipod, was present at the flat bottom of the WZFZ. Further, an mtDNA phylogeny resolved a degree of phylogeographic structure between the B. schellenbergi WZFZ population and four previously sampled Pacific Ocean subduction trench populations, indicating these features are not interconnected through ongoing gene flow. Combined, these data indicate that some amphipods have far broader distributions than previously understood, with some species present in both hadal subduction trenches and non-subduction fracture zones and basins interspersed across the abyssal plains. This initial exploration highlights that whilst non-subduction features are an overlooked minor fraction of the total hadal area, they are essential to our understanding of the ecological and evolutionary dynamics across the hadal zone.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

A global coral reef probability map generated using convolutional neural networks - Jiwei Li; David E. Knapp; Nicholas S. Fabina; Emma V. Kennedy; Kirk Larsen; Mitchell B. Lyons; Nicholas J. Murray; Stuart R. Phinn; Chris M. Roelfsema; Gregory P. Asner (Coral Reefs, 2020)

Extended Pelagic Life in a Bathybenthic Octopus - Roger Villanueva; Vladimir V. Laptikhovsky; Stuart B. Piertney; Fernando Ángel Fernández-Álvarez; Martin A. Collins; Jonathan D. Ablett; Alejandro Escánez (Frontiers in Marine Science, 2020)
Planktonic stages of benthic octopuses can reach relatively large sizes in some species, usually in oceanic, epipelagic waters while living as part of the macroplankton. These young octopuses appear to delay settlement on the seabed for an undetermined period of time that is probably longer than for those octopus paralarvae living in coastal, neritic waters. The reason for this delay is unknown and existing information about their biology is very scarce. Here we report on the presence of juvenile and subadult forms of the bathybenthic octopus Pteroctopus tetracirrhus in oceanic waters of the South and North Atlantic and its association with the pyrosomid species Pyrosoma atlanticum , apparently used by the octopus as a refuge or shelter. The relatively large size of the P. tetracirrhus living in oceanic waters as the individuals reported here, together with the morphological characteristics of this bathybenthic species including its gelatinous body, minute suckers embedded in swollen skin and the deep interbrachial web, indicates that P. tetracirrhus may be considered a model of a transitional octopus species that is colonizing the pelagic environment by avoiding descending to the bathyal benthos. This process seems to occur in the same way as in the supposed origin of the ctenoglossan holopelagic octopods of the families Amphitretidae, Bolitaenidae, and Vitreledonellidae, which have arisen via neoteny from the planktonic paralarval stages of benthic octopuses.

Changes to virus taxonomy and the Statutes ratified by the International Committee on Taxonomy of Viruses (2020) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Donald M. Dempsey; Bas E. Dutilh; Balázs Harrach; Robert L. Harrison; R. Curtis Hendrickson; Sandra Junglen; Nick J. Knowles; et al. (Archives of Virology, 2020)

SoilTemp: A global database of near‐surface temperature - Jonas J. Lembrechts; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Martin Kopecký; Jonathan Lenoir; Miska Luoto; Ilya M. D. Maclean; Olivier Roupsard; Eduardo Fuentes‐Lillo; Rafael A. García; Loïc Pellissier; et al. (Global Change Biology, 2020)
Current analyses and predictions of spatially explicit patterns and processes in ecology most often rely on climate data interpolated from standardized weather stations. This interpolated climate data represents long‐term average thermal conditions at coarse spatial resolutions only. Hence, many climate‐forcing factors that operate at fine spatiotemporal resolutions are overlooked. This is particularly important in relation to effects of observation height (e.g. vegetation, snow and soil characteristics) and in habitats varying in their exposure to radiation, moisture and wind (e.g. topography, radiative forcing or cold‐air pooling). Since organisms living close to the ground relate more strongly to these microclimatic conditions than to free‐air temperatures, microclimatic ground and near‐surface data are needed to provide realistic forecasts of the fate of such organisms under anthropogenic climate change, as well as of the functioning of the ecosystems they live in. To fill this critical gap, we highlight a call for temperature time series submissions to SoilTemp, a geospatial database initiative compiling soil and near‐surface temperature data from all over the world. Currently, this database contains time series from 7,538 temperature sensors from 51 countries across all key biomes. The database will pave the way toward an improved global understanding of microclimate and bridge the gap between the available climate data and the climate at fine spatiotemporal resolutions relevant to most organisms and ecosystem processes.

Controls on Ocean Color Spectra Observed During the North Atlantic Aerosols and Marine Ecosystems Study (NAAMES) - James G. Allen; David A. Siegel; Norman B. Nelson; Stuart Halewood (Frontiers in Marine Science, 2020)

Association mapping of malting quality traits in UK spring and winter barley cultivar collections - Mark E. Looseley; Luke Ramsay; Hazel Bull; J. Stuart Swanston; Paul D. Shaw; Malcolm Macaulay; Allan Booth; Joanne R. Russell; Robbie Waugh; William T. B. Thomas (Theoretical and Applied Genetics, 2020)
Key message Historical malting quality data was collated from UK national and recommended list trial data and used in a GWAS. 25 QTL were identified, with the majority from spring barley cultivar sets. Abstract In Europe, the most economically significant use of barley is the production of malt for use in the brewing and distilling industries. As such, selection for traits related to malting quality is of great commercial interest. In order to study the genetic basis of variation for malting quality traits in UK cultivars, a historical set of trial data was collated from national and recommended list trials from the period 1988 to 2016. This data was used to estimate variety means for 20 quality related traits in 451 spring barley cultivars, and 407 winter cultivars. Genotypes for these cultivars were generated using iSelect 9k and 50k genotyping platforms, and a genome wide association scan performed to identify malting quality quantitative trait loci (QTL). 24 QTL were identified in spring barley cultivars, and 2 from the winter set. A number of these correspond to known malting quality related genes but the remainder represents novel genetic variation that is accessible to breeders for the genetic improvement of new cultivars.

Caveolin-1 Ablation Imparts Partial Protection Against Inner Retinal Injury in Experimental Glaucoma and Reduces Apoptotic Activation - Mojdeh Abbasi; Vivek K. Gupta; Nitin Chitranshi; Veer B. Gupta; Mehdi Mirzaei; Yogita Dheer; Linda Garthwaite; Thiri Zaw; Robert G. Parton; Yuyi You; Stuart L. Graham (Molecular Neurobiology, 2020)

Stroke Induces Prolonged Changes in Lipid Metabolism, the Liver and Body Composition in Mice - Michael J. Haley; Claire S. White; Daisy Roberts; Kelly O’Toole; Catriona J. Cunningham; Jack Rivers-Auty; Conor O’Boyle; Conor Lane; Oliver Heaney; Stuart M. Allan; Catherine B. Lawrence (Translational Stroke Research, 2020)
During recovery, stroke patients are at risk of developing long-term complications that impact quality of life, including changes in body weight and composition, depression and anxiety, as well as an increased risk of subsequent vascular events. The aetiologies and time-course of these post-stroke complications have not been extensively studied and are poorly understood. Therefore, we assessed long-term changes in body composition, metabolic markers and behaviour after middle cerebral artery occlusion in mice. These outcomes were also studied in the context of obesity, a common stroke co-morbidity proposed to protect against post-stroke weight loss in patients. We found that stroke induced long-term changes in body composition, characterised by a sustained loss of fat mass with a recovery of lean weight loss. These global changes in response to stroke were accompanied by an altered lipid profile (increased plasma free fatty acids and triglycerides) and increased adipokine release at 60 days. After stroke, the liver also showed histological changes indicative of liver damage and a decrease in plasma alanine aminotransferase (ALT) was observed. Stroke induced depression and anxiety-like behaviours in mice, illustrated by deficits in exploration, nest building and burrowing behaviours. When initial infarct volumes were matched between mice with and without comorbid obesity, these outcomes were not drastically altered. Overall, we found that stroke induced long-term changes in depressive/anxiety-like behaviours, and changes in plasma lipids, adipokines and the liver that may impact negatively on future vascular health.

Quantifying life history demographics of the scleractinian coral genus Pocillopora at Palmyra Atoll - Sho M. Kodera; Clinton B. Edwards; Vid Petrovic; Nicole E. Pedersen; Yoan Eynaud; Stuart A. Sandin (Coral Reefs, 2020)

Neonatal Organ and Tissue Donation for Research: Options Following Death by Natural Causes - Martha Anderson; Stuart Youngner; Regina Dunne Smith; Raja R. Nandyal; Jeffrey P. Orlowski; B. Jessie Hill; Sarah Gutin Barsman (Cell and Tissue Banking, 2020)

Transcriptional Profiling of Individual Airway Projecting Vagal Sensory Neurons - Stuart B. Mazzone; Luyi Tian; Aung Aung Kywe Moe; Matthew W. Trewella; Matthew E. Ritchie; Alice E. McGovern (Molecular Neurobiology, 2020)

Predicting the spatial distribution of allele frequencies for a gene associated with tolerance to eutrophication and high temperature in the reef-building coral, Acropora millepora, on the Great Barrier Reef - Young K. Jin; Stuart Kininmonth; Petra B. Lundgren; Madeleine J. H. van Oppen; Bette L. Willis (Coral Reefs, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Fish Diet Shifts Associated with the Northern Gulf of Mexico Hypoxic Zone - Cassandra N. Glaspie; Melissa Clouse; Klaus Huebert; Stuart A. Ludsin; Doran M. Mason; James J. Pierson; Michael R. Roman; Stephen B. Brandt (Estuaries and Coasts, 2019)

Changes in benthic community composition associated with the outbreak of the corallimorph, Rhodactis howesii, at Palmyra Atoll - Amanda L. Carter; Clinton B. Edwards; Michael D. Fox; Corinne G. Amir; Yoan Eynaud; Maggie D. Johnson; Levi S. Lewis; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Limited coral mortality following acute thermal stress and widespread bleaching on Palmyra Atoll, central Pacific - Michael D. Fox; Amanda L. Carter; Clinton B. Edwards; Yuichiro Takeshita; Maggie D. Johnson; Vid Petrovic; Corinne G. Amir; Enric Sala; Stuart A. Sandin; Jennifer E. Smith (Coral Reefs, 2019)

Purification of carbamoyl phosphate synthetase 1 (CPS1) from wood frog (Rana sylvatica) liver and its regulation in response to ice-nucleation and subsequent whole-body freezing - Stuart R. Green; Kenneth B. Storey (Molecular and Cellular Biochemistry, 2019)

Genetic swamping and possible species collapse: tracking introgression between the native Candy Darter and introduced Variegate Darter - Isaac Gibson; Amy B. Welsh; Stuart A. Welsh; Daniel A. Cincotta (Conservation Genetics, 2019)

Benefits of genome-edited crops: expert opinion - Rim Lassoued; Diego Maximiliano Macall; Hayley Hesseln; Peter W. B. Phillips; Stuart J. Smyth (Transgenic Research, 2019)

Protecting groundwater levels and ecosystems with simple management approaches - Saskia L. Noorduijn; Peter G. Cook; Craig T. Simmons; Stuart B. Richardson (Hydrogeology Journal, 2019)

Prey nutrient content creates omnivores out of predators - Todd A. Ugine; Stuart B. Krasnoff; Robert J. Grebenok; Spencer T. Behmer; John E. Losey (Ecology Letters, 2019)
The proximate forces that create omnivores out of herbivores and predators have long fascinated ecologists, but the causal reasons for a shift to omnivory are poorly understood. Determining what factors influence changes in trophic position are essential as omnivory plays a central role in theoretical and applied ecology. We used sevenspotted lady beetles ( Coccinella septempunctata ) to test how prey nutrient content affects beetles’ propensity to engage in herbivory. We show that beetles consuming an all‐prey diet demonstrate normal growth and development, but suffer a complete loss of fitness (spermatogenic failure) that is restored via herbivory and supplementation with phytosterols and cholesterol. Furthermore, we show that lady beetles possess a state‐dependent sterol‐specific appetite and redressed their sterol deficit by feeding on foliage. These results demonstrate that predators balance their nutrient intake via herbivory when prey quality is low, and reveal a selective force (sterol nutrition) that drives predatory taxa to omnivory.

Using meta‐omics of contaminated sediments to monitor changes in pathways relevant to climate regulation - Simone C. Birrer; Katherine A. Dafforn; Melanie Y. Sun; Rohan B. H. Williams; Jaimie Potts; Peter Scanes; Brendan P. Kelaher; Stuart L. Simpson; Staffan Kjelleberg; Sanjay Swarup; Peter Steinberg; Emma L. Johnston (Environmental Microbiology, 2019)
Summary Microbially mediated biogeochemical processes are crucial for climate regulation and may be disrupted by anthropogenic contaminants. To better manage contaminants, we need tools that make real‐time causal links between stressors and altered microbial functions, and the potential consequences for ecosystem services such as climate regulation. In a manipulative field experiment, we used metatranscriptomics to investigate the impact of excess organic enrichment and metal contamination on the gene expression of nitrogen and sulfur metabolisms in coastal sediments. Our gene expression data suggest that excess organic enrichment results in (i) higher transcript levels of genes involved in the production of toxic ammonia and hydrogen sulfide and (ii) lower transcript levels associated with the degradation of a greenhouse gas (nitrous oxide). However, metal contamination did not have any significant impact on gene expression. We reveal the genetic mechanisms that may lead to altered productivity and greenhouse gas production in coastal sediments due to anthropogenic contaminants. Our data highlight the applicability of metatranscriptomics as a management tool that provides an immense breadth of information and can identify potentially impacted process measurements that need further investigation.

Effects of hybridization on sea turtle fitness - Luciano S. Soares; Karen A. Bjorndal; Alan B. Bolten; Maria A. G. dei Marcovaldi; Pedro B. Luz; Rodrigo Machado; Rachel Lo; Stuart F. McDaniel; Adam C. Payton; Thomas B. Waltzek; Marta L. Wayne (Conservation Genetics, 2018)

Reflex regulation of breathing by the paratrigeminal nucleus via multiple bulbar circuits - Alexandria K. Driessen; Michael J. Farrell; Mathias Dutschmann; Davor Stanic; Alice E. McGovern; Stuart B. Mazzone (Brain Structure and Function, 2018)

Effects of Pollution From Anthropogenic Point Sources on the Recruitment of Sessile Estuarine Reef Biota - Amelia E. Fowles; Graham J. Edgar; Rick D. Stuart-Smith; James B. Kirkpatrick; Nicole Hill; Russell J. Thomson; Elisabeth M. A. Strain (Frontiers in Marine Science, 2018)

Variation in DNA methylation is associated with migratory phenotypes of lake sturgeon Acipenser fulvescens in the St. Clair River, MI, USA - Justine M. Whitaker; Amy B. Welsh; Darryl W. Hondorp; James C. Boase; George T. Merovich; Stuart Welsh; Charles Krueger (Journal of Fish Biology, 2018)
Lake sturgeon Acipenser fulvescens populations show a variety of movement patterns that are poorly understood. To compare two migratory phenotypes of A. fulvescens in the St. Clair River, MI, USA, multiple data types were analysed. Individual fish were classified into migratory phenotypes based on acoustic telemetry data collected 2012–2015. Acipenser fulvescens consistently showed movement from the St. Clair River upriver into Lake Huron or downriver into Lake St. Clair. The two migratory phenotypes were then compared for differences in morphometrics, genetics and epigenetics. Morphological differences based on linear measurements were not detected between phenotypes. Microsatellite data from 11 loci suggested one population with no genetic differentiation between migratory phenotypes. Our epigenetic results indicated that the migratory phenotypes are differentially methylated ( P A. fulvescens . Only one restriction site was identified to be driving the differential methylation ( P A. fulvescens , DNA methylation may play a role in the observed movement pattern variation. When combined with microsatellite and morphometric analyses, our results suggested that different migratory patterns may reflect phenotypic plasticity, allowing A. fulvescens to acclimate to short‐term environmental variability. Without an integrated approach, the role of epigenetics in the migratory phenotype of A. fulvescens may have been overlooked. Further characterization of migratory phenotypes could be important for management to conserve behavioural variation across the distribution of A. fulvescens and for design of stocking guidelines.

Differential Morphological and Biochemical Recovery from Chemotherapy-Induced Peripheral Neuropathy Following Paclitaxel, Ixabepilone, or Eribulin Treatment in Mouse Sciatic Nerves - B. M. Cook; K. M. Wozniak; D. A. Proctor; R. B. Bromberg; Y. Wu; B. S. Slusher; B. A. Littlefield; M. A. Jordan; L. Wilson; Stuart C. Feinstein (Neurotoxicity Research, 2018)

Rapid ecosystem service assessment of the impact of Koshi Tappu Wildlife Reserve on wetland benefits to local communities - Jennifer C. Merriman; Hum Gurung; Shalu Adhikari; Stuart H. M. Butchart; Top B. Khatri; Ravi S. Pandit; Ashok K. Ram; David H. L. Thomas; Ishana Thapa (Wetlands Ecology and Management, 2018)

The adoption of automated phenotyping by plant breeders - Lana Awada; Peter W. B. Phillips; Stuart J. Smyth (Euphytica, 2018)
Phenomics or automated phenotyping (AP) is an emerging approach, identified as a priority for future crop breeding research. This approach promises to provide accurate, precise, fast, large-scale, and accumulated phenotyping data which when integrated with corresponding genomic and environmental data is expected to trigger a great leap forward in plant breeding. However, despite promising applications, AP adoption in plant breeding is still in its infancy. It is unclear to many plant breeders how or if much of the enormous volume, diversity, and velocity of imaging and remote-sensing data generated by AP is going to be usefully integrated into breeding programs. This paper develops an economical model of heterogeneous breeders’ decision-making to examine adoption decisions regarding whether to adopt AP or continue using conventional phenotyping. The results of this model indicate that many interlocking factors, including genetic gain/expected return, variable and sunk costs, subsequent rate of technology improvement, and breeders’ level of aversion to AP, are at work as breeders determine whether to adopt AP. This study also provides a numerical example to show the impact of breeders’ aversion toward the adoption of a new technology (e.g., AP) on the expected return generated from breeding a new wheat variety.

Taxonomy of the family Arenaviridae and the order Bunyavirales: update 2018 - Piet Maes; Sergey V. Alkhovsky; Yīmíng Bào; Martin Beer; Monica Birkhead; Thomas Briese; Michael J. Buchmeier; Charles H. Calisher; Rémi N. Charrel; Il Ryong Choi; Christopher S. Clegg; Juan Carlos de la Torre; et al. (Archives of Virology, 2018)

Taxonomy of the order Mononegavirales: update 2018 - Gaya K. Amarasinghe; Nidia G. Aréchiga Ceballos; Ashley C. Banyard; Christopher F. Basler; Sina Bavari; Andrew J. Bennett; Kim R. Blasdell; Thomas Briese; Alexander Bukreyev; Yíngyún Caì; Charles H. Calisher; Cristine Campos Lawson; et al. (Archives of Virology, 2018)

These aren’t the loci you’e looking for: Principles of effective SNP filtering for molecular ecologists - Shannon J. O'Leary; Jonathan B. Puritz; Stuart C. Willis; Christopher M. Hollenbeck; David S. Portnoy (Molecular Ecology, 2018)
Sequencing reduced‐representation libraries of restriction site‐associated DNA ( RAD seq) to identify single nucleotide polymorphisms ( SNP s) is quickly becoming a standard methodology for molecular ecologists. Because of the scale of RAD seq data sets, putative loci cannot be assessed individually, making the process of filtering noise and correctly identifying biologically meaningful signal more difficult. Artefacts introduced during library preparation and/or bioinformatic processing of SNP data can create patterns that are incorrectly interpreted as indicative of population structure or natural selection. Therefore, it is crucial to carefully consider types of errors that may be introduced during laboratory work and data processing, and how to minimize, detect and remove these errors. Here, we discuss issues inherent to RAD seq methodologies that can result in artefacts during library preparation and locus reconstruction resulting in erroneous SNP calls and, ultimately, genotyping error. Further, we describe steps that can be implemented to create a rigorously filtered data set consisting of markers accurately representing independent loci and compare the effect of different combinations of filters on four RAD data sets. At last, we stress the importance of publishing raw sequence data along with final filtered data sets in addition to detailed documentation of filtering steps and quality control measures.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Correction to: Progressive multifocal leukoencephalopathy in rituximab-treated rheumatic diseases: a rare event - Joseph R. Berger; Vineeta Malik; Stuart Lacey; Paul Brunetta; Patricia B. Lehane (Journal of NeuroVirology, 2018)

Progressive multifocal leukoencephalopathy in rituximab-treated rheumatic diseases: a rare event - Joseph R. Berger; Vineeta Malik; Stuart Lacey; Paul Brunetta; Patricia B. Lehane (Journal of NeuroVirology, 2018)

Impact of multiple stressors on juvenile fish in estuaries of the northeast Pacific - Jason D. Toft; Stuart H. Munsch; Jeffery R. Cordell; Kiira Siitari; Van C. Hare; Brett M. Holycross; Lisa A. DeBruyckere; Correigh M. Greene; Brent B. Hughes (Global Change Biology, 2018)
A key step in identifying global change impacts on species and ecosystems is to quantify effects of multiple stressors. To date, the science of global change has been dominated by regional field studies, experimental manipulation, meta‐analyses, conceptual models, reviews, and studies focusing on a single stressor or species over broad spatial and temporal scales. Here, we provide one of the first studies for coastal systems examining multiple stressor effects across broad scales, focused on the nursery function of 20 estuaries spanning 1,600 km of coastline, 25 years of monitoring, and seven fish and invertebrate species along the northeast Pacific coast. We hypothesized those species most estuarine dependent and negatively impacted by human activities would have lower presence and abundances in estuaries with greater anthropogenic land cover, pollution, and water flow stress. We found significant negative relationships between juveniles of two of seven species (Chinook salmon and English sole) and estuarine stressors. Chinook salmon were less likely to occur and were less abundant in estuaries with greater pollution stress. They were also less abundant in estuaries with greater flow stress, although this relationship was marginally insignificant. English sole were less abundant in estuaries with greater land cover stress. Together, we provide new empirical evidence that effects of stressors on two fish species culminate in detectable trends along the northeast Pacific coast, elevating the need for protection from pollution, land cover, and flow stressors to their habitats. Lack of response among the other five species could be related to differing resistance to specific stressors, type and precision of the stressor metrics, and limitations in catch data across estuaries and habitats. Acquiring improved measurements of impacts to species will guide future management actions, and help predict how estuarine nursery functions can be optimized given anthropogenic stressors and climate change scenarios.

How complex should models be? Comparing correlative and mechanistic range dynamics models - Damien A. Fordham; Cleo Bertelsmeier; Barry W. Brook; Regan Early; Dora Neto; Stuart C. Brown; Sébastien Ollier; Miguel B. Araújo (Global Change Biology, 2018)
Criticism has been levelled at climate‐change‐induced forecasts of species range shifts that do not account explicitly for complex population dynamics. The relative importance of such dynamics under climate change is, however, undetermined because direct tests comparing the performance of demographic models vs. simpler ecological niche models are still lacking owing to difficulties in evaluating forecasts using real‐world data. We provide the first comparison of the skill of coupled ecological‐niche‐population models and ecological niche models in predicting documented shifts in the ranges of 20 British breeding bird species across a 40‐year period. Forecasts from models calibrated with data centred on 1970 were evaluated using data centred on 2010. We found that more complex coupled ecological‐niche‐population models (that account for dispersal and metapopulation dynamics) tend to have higher predictive accuracy in forecasting species range shifts than structurally simpler models that only account for variation in climate. However, these better forecasts are achieved only if ecological responses to climate change are simulated without static snapshots of historic land use, taken at a single point in time. In contrast, including both static land use and dynamic climate variables in simpler ecological niche models improve forecasts of observed range shifts. Despite being less skilful at predicting range changes at the grid‐cell level, ecological niche models do as well, or better, than more complex models at predicting the magnitude of relative change in range size. Therefore, ecological niche models can provide a reasonable first approximation of the magnitude of species' potential range shifts, especially when more detailed data are lacking on dispersal dynamics, demographic processes underpinning population performance, and change in land cover.

Author Correction to: Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Size-mediated control of perch–midge coupling in Lake Erie transient dead zones - Daisuke Goto; James J. Roberts; Steven A. Pothoven; Stuart A. Ludsin; Henry A. Vanderploeg; Stephen B. Brandt; Tomas O. Höök (Environmental Biology of Fishes, 2017)

Large-area imaging reveals biologically driven non-random spatial patterns of corals at a remote reef - Clinton B. Edwards; Yoan Eynaud; Gareth J. Williams; Nicole E. Pedersen; Brian J. Zgliczynski; Arthur C. R. Gleason; Jennifer E. Smith; Stuart A. Sandin (Coral Reefs, 2017)

An incipient invasion of brown anole lizards (Anolis sagrei) into their own native range in the Cayman Islands: a case of cryptic back-introduction - Jason J. Kolbe; Johanna E. Wegener; Yoel E. Stuart; Ushuaia Milstead; Katherine E. Boronow; Alexis S. Harrison; Jonathan B. Losos (Biological Invasions, 2017)

Climate change as a long-term stressor for the fisheries of the Laurentian Great Lakes of North America - Paris D. Collingsworth; David B. Bunnell; Michael W. Murray; Yu-Chun Kao; Zachary S. Feiner; Randall M. Claramunt; Brent M. Lofgren; Tomas O. Höök; Stuart A. Ludsin (Reviews in Fish Biology and Fisheries, 2017)

50 years of the International Committee on Taxonomy of Viruses: progress and prospects - Michael J. Adams; Elliot J. Lefkowitz; Andrew M. Q. King; Balázs Harrach; Robert L. Harrison; Nick J. Knowles; Andrew M. Kropinski; Mart Krupovic; Jens H. Kuhn; Arcady R. Mushegian; Max L. Nibert; Sead Sabanadzovic; et al. (Archives of Virology, 2017)

Mass‐flowering crops dilute pollinator abundance in agricultural landscapes across Europe - Andrea Holzschuh; Matteo Dainese; Juan P. González‐Varo; Sonja Mudri‐Stojnić; Verena Riedinger; Maj Rundlöf; Jeroen Scheper; Jennifer B. Wickens; Victoria J. Wickens; Riccardo Bommarco; David Kleijn; Simon G. Potts; et al. (Ecology Letters, 2016)
Mass‐flowering crops ( MFC s) are increasingly cultivated and might influence pollinator communities in MFC fields and nearby semi‐natural habitats ( SNH s). Across six European regions and 2 years, we assessed how landscape‐scale cover of MFC s affected pollinator densities in 408 MFC fields and adjacent SNH s. In MFC fields, densities of bumblebees, solitary bees, managed honeybees and hoverflies were negatively related to the cover of MFC s in the landscape. In SNH s, densities of bumblebees declined with increasing cover of MFC s but densities of honeybees increased. The densities of all pollinators were generally unrelated to the cover of SNH s in the landscape. Although MFC fields apparently attracted pollinators from SNH s, in landscapes with large areas of MFC s they became diluted. The resulting lower densities might negatively affect yields of pollinator‐dependent crops and the reproductive success of wild plants. An expansion of MFC s needs to be accompanied by pollinator‐supporting practices in agricultural landscapes.

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Adaptive and neutral genetic differentiation among Scottish and endangered Irish red grouse (Lagopus lagopus scotica) - Yvonne Meyer-Lucht; Kevin P. Mulder; Marianne C. James; Barry J. McMahon; Kieran Buckley; Stuart B. Piertney; Jacob Höglund (Conservation Genetics, 2016)

Is the Alzheimer’s disease cortical thickness signature a biological marker for memory? - Edgar Busovaca; Molly E. Zimmerman; Irene B. Meier; Erica Y. Griffith; Stuart M. Grieve; Mayuresh S. Korgaonkar; Leanne M. Williams; Adam M. Brickman (Brain Imaging and Behavior, 2016)

Stochastic dilution effects weaken deterministic effects of niche‐based processes in species rich forests - Xugao Wang; Thorsten Wiegand; Nathan J. B. Kraft; Nathan G. Swenson; Stuart J. Davies; Zhanqing Hao; Robert Howe; Yiching Lin; Keping Ma; Xiangcheng Mi; Sheng‐Hsin Su; I‐Fang Sun; et al. (Ecology, 2016)
Recent theory predicts that stochastic dilution effects may result in species‐rich communities with statistically independent species spatial distributions, even if the underlying ecological processes structuring the community are driven by deterministic niche differences. Stochastic dilution is a consequence of the stochastic geometry of biodiversity where the identities of the nearest neighbors of individuals of a given species are largely unpredictable. Under such circumstances, the outcome of deterministic species interactions may vary greatly among individuals of a given species. Consequently, nonrandom patterns in the biotic neighborhoods of species, which might be expected from coexistence or community assembly theory (e.g., individuals of a given species are neighbored by phylogenetically similar species), are weakened or do not emerge, resulting in statistical independence of species spatial distributions. We used data on phylogenetic and functional similarity of tree species in five large forest dynamics plots located across a gradient of species richness to test predictions of the stochastic dilution hypothesis. To quantify the biotic neighborhood of a focal species we used the mean phylogenetic (or functional) dissimilarity of the individuals of the focal species to all species within a local neighborhood. We then compared the biotic neighborhood of species to predictions from stochastic null models to test if a focal species was surrounded by more or less similar species than expected by chance. The proportions of focal species that showed spatial independence with respect to their biotic neighborhoods increased with total species richness. Locally dominant, high‐abundance species were more likely to be surrounded by species that were statistically more similar or more dissimilar than expected by chance. Our results suggest that stochasticity may play a stronger role in shaping the spatial structure of species rich tropical forest communities than it does in species poorer forests. These findings represent an important step towards understanding the factors that govern the spatial configuration of local biotic communities. The stochastic dilution effect is a simple geometric mechanism that can explain why species’ spatial distributions in species‐rich communities approximate independence from their biotic neighborhood, even if deterministic niche processes are in effect.

The role of parasite‐driven selection in shaping landscape genomic structure in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Alex Douglas; Marianne C. James; Steve M. Redpath; Stuart B. Piertney (Molecular Ecology, 2016)
Landscape genomics promises to provide novel insights into how neutral and adaptive processes shape genome‐wide variation within and among populations. However, there has been little emphasis on examining whether individual‐based phenotype–genotype relationships derived from approaches such as genome‐wide association (GWAS) manifest themselves as a population‐level signature of selection in a landscape context. The two may prove irreconcilable as individual‐level patterns become diluted by high levels of gene flow and complex phenotypic or environmental heterogeneity. We illustrate this issue with a case study that examines the role of the highly prevalent gastrointestinal nematode Trichostrongylus tenuis in shaping genomic signatures of selection in red grouse ( Lagopus lagopus scotica ). Individual‐level GWAS involving 384 SNPs has previously identified five SNPs that explain variation in T. tenuis burden. Here, we examine whether these same SNPs display population‐level relationships between T. tenuis burden and genetic structure across a small‐scale landscape of 21 sites with heterogeneous parasite pressure. Moreover, we identify adaptive SNPs showing signatures of directional selection using outlier analysis and relate population‐ and individual‐level patterns of multilocus neutral and adaptive genetic structure to T. tenuis burden. The five candidate SNPs for parasite‐driven selection were neither associated with T. tenuis burden on a population level, nor under directional selection. Similarly, there was no evidence of parasite‐driven selection in SNPs identified as candidates for directional selection. We discuss these results in the context of red grouse ecology and highlight the broader consequences for the utility of landscape genomics approaches for identifying signatures of selection.

Incomplete coexistence systems and international food trade impacts - Stuart J. Smyth; Peter W. B. Phillips (Transgenic Research, 2015)

Evidence for multiple sensory circuits in the brain arising from the respiratory system: an anterograde viral tract tracing study in rodents - Alice E. McGovern; Nicholas Davis-Poynter; Seung-Kwon Yang; David G. Simmons; Michael J. Farrell; Stuart B. Mazzone (Brain Structure and Function, 2015)

Gene dynamics of toll-like receptor 4 through a population bottleneck in an insular population of water voles (Arvicola amphibius) - Martha K. Gavan; Matthew K. Oliver; Alex Douglas; Stuart B. Piertney (Conservation Genetics, 2015)

Erratum to: Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2015)

Genome‐wide association and genome partitioning reveal novel genomic regions underlying variation in gastrointestinal nematode burden in a wild bird - Marius A. Wenzel; Marianne C. James; Alex Douglas; Stuart B. Piertney (Molecular Ecology, 2015)
Identifying the genetic architecture underlying complex phenotypes is a notoriously difficult problem that often impedes progress in understanding adaptive eco‐evolutionary processes in natural populations. Host–parasite interactions are fundamentally important drivers of evolutionary processes, but a lack of understanding of the genes involved in the host's response to chronic parasite insult makes it particularly difficult to understand the mechanisms of host life history trade‐offs and the adaptive dynamics involved. Here, we examine the genetic basis of gastrointestinal nematode ( Trichostrongylus tenuis ) burden in 695 red grouse ( Lagopus lagopus scotica ) individuals genotyped at 384 genome‐wide SNPs. We first use genome‐wide association to identify individual SNPs associated with nematode burden. We then partition genome‐wide heritability to identify chromosomes with greater heritability than expected from gene content, due to harbouring a multitude of additive SNPs with individually undetectable effects. We identified five SNPs on five chromosomes that accounted for differences of up to 556 worms per bird, but together explained at best 4.9% of the phenotypic variance. These SNPs were closely linked to genes representing a range of physiological processes including the immune system, protein degradation and energy metabolism. Genome partitioning indicated genome‐wide heritability of up to 29% and three chromosomes with excess heritability of up to 4.3% (total 8.9%). These results implicate SNPs and novel genomic regions underlying nematode burden in this system and suggest that this phenotype is somewhere between being based on few large‐effect genes (oligogenic) and based on a large number of genes with small individual but large combined effects (polygenic).

Managing produced water from coal seam gas projects: implications for an emerging industry in Australia - Peter J. Davies; Damian B. Gore; Stuart J. Khan (Environmental Science and Pollution Research, 2015)

A home away from home: insights from successful leopard (Panthera pardus) translocations - Florian J. Weise; Joseph Lemeris; Ken J. Stratford; Rudie J. van Vuuren; Stuart J. Munro; Stuart J. Crawford; Laurie L. Marker; Andrew B. Stein (Biodiversity and Conservation, 2015)

In silico identification and characterisation of 17 polymorphic anonymous non-coding sequence markers (ANMs) for red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Stuart B. Piertney (Conservation Genetics Resources, 2015)

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams - Thomas B. Parr; Christopher S. Cronan; Tsutomu Ohno; Stuart E. G. Findlay; Sean M. C. Smith; Kevin S. Simon (Limnology and Oceanography, 2015)
Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom‐up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a gradient of urbanization in central and southern Maine and used elemental and optical analyses, including parallel factor analysis of excitation‐emission matrices, to characterize DOM composition. Results show that fluorescent and stoichiometric DOM composition changed significantly across the rural to urban gradient. Specifically, the proportion of humic‐like allochthonous DOM decreased while that of more bioavailable autochthonous DOM increased in the more urbanized streams. In laboratory incubations, increased autochthonous DOM was associated with a doubling in the decay rate of dissolved organic carbon as well as increased activity of C‐acquiring enzymes. These results suggest that urbanization replaces upstream humic material with more local sources of DOM that turnover more rapidly and may drive bottom‐up changes in microbial communities and affect the quality and quantity of downstream DOM delivery.

Consensus Paper: Radiological Biomarkers of Cerebellar Diseases - Leonardo Baldarçara; Stuart Currie; M. Hadjivassiliou; Nigel Hoggard; Allison Jack; Andrea P. Jackowski; Mario Mascalchi; Cecilia Parazzini; Kathrin Reetz; Andrea Righini; Jörg B. Schulz; Alessandra Vella; et al. (The Cerebellum, 2015)

Effect of a Medical Toxicology Admitting Service on Length of Stay, Cost, and Mortality Among Inpatients Discharged with Poisoning-Related Diagnoses - Steven C. Curry; Daniel E. Brooks; Aaron B. Skolnik; Richard D. Gerkin; Stuart Glenn (Journal of Medical Toxicology, 2015)

Identification and characterisation of 17 polymorphic candidate genes for response to parasitic nematode (Trichostrongylus tenuis) infection in red grouse (Lagopus lagopus scotica) - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; Stuart B. Piertney (Conservation Genetics Resources, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Potential impact of invasive alien species on ecosystem services provided by a tropical forested ecosystem: a case study from Montserrat - Kelvin S.-H. Peh; Andrew Balmford; Jennifer C. Birch; Claire Brown; Stuart H. M. Butchart; James Daley; Jeffrey Dawson; Gerard Gray; Francine M. R. Hughes; Stephen Mendes; James Millett; Alison J. Stattersfield; et al. (Biological Invasions, 2015)

Resolving issues with environmental impact assessment of marine renewable energy installations - Ilya M. D. Maclean; Richard Inger; David Benson; Cormac G. Booth; Clare B. Embling; W. James Grecian; Johanna J. Heymans; Kate E. Plummer; Michael Shackshaft; Carol E. Sparling; Ben Wilson; Lucy J. Wright; et al. (Frontiers in Marine Science, 2014)

Novel molecular approach demonstrates that turbid river plumes reduce predation mortality on larval fish - Lucia B. Carreon‐Martinez; Kyle W. Wellband; Timothy B. Johnson; Stuart A. Ludsin; Daniel D. Heath (Molecular Ecology, 2014)
Turbidity associated with river plumes is known to affect the search ability of visual predators and thus can drive ‘top‐down’ impacts on prey populations in complex ecosystems; however, traditional quantification of predator–prey relationships (i.e. stomach content analysis) often fails with larval fish due to rapid digestion rates. Herein, we use novel molecular genetic methods to quantify larval yellow perch ( YP ) in predator stomachs in western Lake Erie to test the hypothesis that turbidity drives variation in larval predation. We characterize predator stomach content DNA to first identify YP DNA (single nucleotide polymorphism) and then quantify larval YP predation (microsatellite allele counting) in two river plumes differing in turbidity. Our results showed elevated larval YP predation in the less turbid river plume, consistent with a top‐down impact of turbidity on larval survival. Our analyses highlight novel ecological hypothesis testing using the power of innovative molecular genetic approaches.

Fine‐scale population epigenetic structure in relation to gastrointestinal parasite load in red grouse ( Lagopus lagopus scotica ) - Marius A. Wenzel; Stuart B. Piertney (Molecular Ecology, 2014)
Epigenetic modification of cytosine methylation states can be elicited by environmental stresses and may be a key process affecting phenotypic plasticity and adaptation. Parasites are potent stressors with profound physiological and ecological effects on their host, but there is little understanding in how parasites may influence host methylation states. Here, we estimate epigenetic diversity and differentiation among 21 populations of red grouse ( Lagopus lagopus scotica ) in north‐east Scotland and test for association of gastrointestinal parasite load (caecal nematode Trichostrongylus tenuis ) with hepatic genome‐wide and locus‐specific methylation states. Following methylation‐sensitive AFLP (MSAP), 129 bands, representing 73 methylation‐susceptible and 56 nonmethylated epiloci, were scored across 234 individuals. The populations differed significantly in genome‐wide methylation levels and were also significantly epigenetically ( F SC = 0.0227; P F SC = 0.0058; P F ST outliers) using bayescan software and significant positive and negative association of 35 methylation states with parasite load from bespoke generalized estimating equations (GEE), simple logistic regression ( sam ) and Bayesian environmental analysis ( bayenv 2). Following Sanger sequencing, genome mapping and geneontology ( go ) annotation, some of these epiloci were linked to genes involved in regulation of cell cycle, signalling, metabolism, immune system and notably rRNA methylation, histone acetylation and small RNAs. These findings demonstrate an epigenetic signature of parasite load in populations of a wild bird and suggest intriguing physiological effects of parasite‐associated cytosine methylation.

Mechanisms underpinning climatic impacts on natural populations: altered species interactions are more important than direct effects - Nancy Ockendon; David J. Baker; Jamie A. Carr; Elizabeth C. White; Rosamunde E. A. Almond; Tatsuya Amano; Esther Bertram; Richard B. Bradbury; Cassie Bradley; Stuart H. M. Butchart; Nathalie Doswald; Wendy Foden; et al. (Global Change Biology, 2014)
Shifts in species' distribution and abundance in response to climate change have been well documented, but the underpinning processes are still poorly understood. We present the results of a systematic literature review and meta‐analysis investigating the frequency and importance of different mechanisms by which climate has impacted natural populations. Most studies were from temperate latitudes of North America and Europe; almost half investigated bird populations. We found significantly greater support for indirect, biotic mechanisms than direct, abiotic mechanisms as mediators of the impact of climate on populations. In addition, biotic effects tended to have greater support than abiotic factors in studies of species from higher trophic levels. For primary consumers, the impact of climate was equally mediated by biotic and abiotic mechanisms, whereas for higher level consumers the mechanisms were most frequently biotic, such as predation or food availability. Biotic mechanisms were more frequently supported in studies that reported a directional trend in climate than in studies with no such climatic change, although sample sizes for this comparison were small. We call for more mechanistic studies of climate change impacts on populations, particularly in tropical systems.

Mantle heat drives hydrothermal fluids responsible for carbonate-hosted base metal deposits: evidence from 3He/4He of ore fluids in the Irish Pb-Zn ore district - B. Davidheiser-Kroll; F. M. Stuart; A. J. Boyce (Mineralium Deposita, 2014)

Multilocation Corn Stover Harvest Effects on Crop Yields and Nutrient Removal - Douglas L. Karlen; Stuart J. Birrell; Jane M. F. Johnson; Shannon L. Osborne; Thomas E. Schumacher; Gary E. Varvel; Richard B. Ferguson; Jeff M. Novak; James R. Fredrick; John M. Baker; John A. Lamb; Paul R. Adler; et al. (BioEnergy Research, 2014)

Adaptations of aortic and pulmonary artery flow parameters measured by phase-contrast magnetic resonance angiography during supine aerobic exercise - Guido E. Pieles; Gergely Szantho; Jonathan C. L. Rodrigues; Christopher B. Lawton; A. Graham Stuart; Chiara Bucciarelli-Ducci; Mark S. Turner; Craig A. Williams; Robert M. R. Tulloh; Mark C. K. Hamilton (European Journal of Applied Physiology, 2014)

Gradient compression garments protect against orthostatic intolerance during recovery from bed rest - Michael B. Stenger; Stuart M. C. Lee; L. Christine Ribeiro; Tiffany R. Phillips; Robert J. Ploutz-Snyder; Michael C. Willig; Christian M. Westby; Steven H. Platts (European Journal of Applied Physiology, 2014)

Resilience to Stress and Disturbance, and Resistance to Bromus tectorum L. Invasion in Cold Desert Shrublands of Western North America - Jeanne C. Chambers; Bethany A. Bradley; Cynthia S. Brown; Carla D’Antonio; Matthew J. Germino; James B. Grace; Stuart P. Hardegree; Richard F. Miller; David A. Pyke (Ecosystems, 2014)

A taxonomic comparison of local habitat niches of tropical trees - Claire A. Baldeck; Steven W. Kembel; Kyle E. Harms; Joseph B. Yavitt; Robert John; Benjamin L. Turner; George B. Chuyong; David Kenfack; Duncan W. Thomas; Sumedha Madawala; Nimal Gunatilleke; Savitri Gunatilleke; et al. (Oecologia, 2013)

Is There a Role for Human-Dominated Landscapes in the Long-Term Conservation Management of the Critically Endangered Kipunji (Rungwecebus kipunji)? - Claire E. Bracebridge; Tim R. B. Davenport; Vicky F. Mbofu; Stuart J. Marsden (International Journal of Primatology, 2013)

Periprosthetic osteolysis after total hip replacement: molecular pathology and clinical management - Donald W. Howie; Susan D. Neale; David R. Haynes; Oksana T. Holubowycz; Margaret A. McGee; Lucian B. Solomon; Stuart A. Callary; Gerald J. Atkins; David M. Findlay (Inflammopharmacology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for filovirus strains and variants rescued from cDNA - Jens H. Kuhn; Yīmíng Bào; Sina Bavari; Stephan Becker; Steven Bradfute; Kristina Brauburger; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; et al. (Archives of Virology, 2013)

Corrigendum to Cameron et al . 2013 - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

Virus nomenclature below the species level: a standardized nomenclature for laboratory animal-adapted strains and variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Yíngyún Caì; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; et al. (Archives of Virology, 2013)

Eco‐evolutionary dynamics in response to selection on life‐history - Tom C. Cameron; Daniel O'Sullivan; Alan Reynolds; Stuart B. Piertney; Tim G. Benton (Ecology Letters, 2013)
Understanding the consequences of environmental change on ecological and evolutionary dynamics is inherently problematic because of the complex interplay between them. Using invertebrates in microcosms, we characterise phenotypic, population and evolutionary dynamics before, during and after exposure to a novel environment and harvesting over 20 generations. We demonstrate an evolved change in life‐history traits (the age‐ and size‐at‐maturity, and survival to maturity) in response to selection caused by environmental change (wild to laboratory) and to harvesting (juvenile or adult). Life‐history evolution, which drives changes in population growth rate and thus population dynamics, includes an increase in age‐to‐maturity of 76% (from 12.5 to 22 days) in the unharvested populations as they adapt to the new environment. Evolutionary responses to harvesting are outweighed by the response to environmental change (~ 1.4 vs. 4% change in age‐at‐maturity per generation). The adaptive response to environmental change converts a negative population growth trajectory into a positive one: an example of evolutionary rescue.

Consequences of defaunation for a tropical tree community - Rhett D Harrison; Sylvester Tan; Joshua B. Plotkin; Ferry Slik; Matteo Detto; Tania Brenes; Akira Itoh; Stuart J. Davies (Ecology Letters, 2013)
Hunting affects a considerably greater area of the tropical forest biome than deforestation and logging combined. Often even large remote protected areas are depleted of a substantial proportion of their vertebrate fauna. However, understanding of the long‐term ecological consequences of defaunation in tropical forests remains poor. Using tree census data from a large‐scale plot monitored over a 15‐year period since the approximate onset of intense hunting, we provide a comprehensive assessment of the immediate consequences of defaunation for a tropical tree community. Our data strongly suggest that over‐hunting has engendered pervasive changes in tree population spatial structure and dynamics, leading to a consistent decline in local tree diversity over time. However, we do not find any support for suggestions that over‐hunting reduces above‐ground biomass or biomass accumulation rate in this forest. To maintain critical ecosystem processes in tropical forests increased efforts are required to protect and restore wildlife populations.

Individual variation in dispersal associated with phenotype influences fine-scale genetic structure in weasels - Allan D. McDevitt; Matthew K. Oliver; Stuart B. Piertney; Paulina A. Szafrańska; Marek Konarzewski; Karol Zub (Conservation Genetics, 2013)

A comprehensive review of climate adaptation in the United States: more than before, but less than needed - Rosina Bierbaum; Joel B. Smith; Arthur Lee; Maria Blair; Lynne Carter; F. Stuart Chapin; Paul Fleming; Susan Ruffo; Missy Stults; Shannon McNeeley; Emily Wasley; Laura Verduzco (Mitigation and Adaptation Strategies for Global Change, 2013)

A transcriptomic investigation of handicap models in sexual selection - Marius A. Wenzel; Lucy M. I. Webster; Steve Paterson; François Mougeot; Jesús Martínez-Padilla; Stuart B. Piertney (Behavioral Ecology and Sociobiology, 2013)

Virus nomenclature below the species level: a standardized nomenclature for natural variants of viruses assigned to the family Filoviridae - Jens H. Kuhn; Yiming Bao; Sina Bavari; Stephan Becker; Steven Bradfute; J. Rodney Brister; Alexander A. Bukreyev; Kartik Chandran; Robert A. Davey; Olga Dolnik; John M. Dye; Sven Enterlein; et al. (Archives of Virology, 2013)

The Frequency of Antibiotic-Resistant Bacteria in Homes Differing in Their Use of Surface Antibacterial Agents - Bonnie M. Marshall; Eduardo Robleto; Theresa Dumont; Stuart B. Levy (Current Microbiology, 2012)

Pronounced genetic structure and low genetic diversity in European red-billed chough (Pyrrhocorax pyrrhocorax) populations - Marius A. Wenzel; Lucy M. I. Webster; Guillermo Blanco; Malcolm D. Burgess; Christian Kerbiriou; Gernot Segelbacher; Stuart B. Piertney; Jane M. Reid (Conservation Genetics, 2012)

Littoral‐zone influences on particulate organic matter composition along the freshwater‐tidal Hudson River, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2012)
A multi‐tracer approach was applied to particulate organic material (POM) biogeochemistry along a 165‐km transect of the freshwater‐tidal portion of the Hudson River estuary (HRE). Elemental carbon and nitrogen, stable isotopes, chlorophyll a , and lignin phenols were measured monthly at a mid‐estuary station from August to November 2007, and monthly at the same station and 3–5 additional stations in 2008. POM at stations proximal to major tidal wetland and aquatic vegetation (WETAV) zones showed ∼ 2‰ higher carbon isotopic signature of particulate organic carbon ( δ 13 C POC ), ∼ 3‰ higher nitrogen isotopic signature of particulate nitrogen ( δ 15 N PN ), elevated chlorophyll a levels, and up to 3‐fold increases in Λ 8 ‐lignin phenols indicative of relatively fresh plant matter. This prominent shift in POM composition suggests that WETAV areas supply compositionally unique organic matter along the HRE, especially during low flow. Based on shifts in geochemical tracers downstream of the largest WETAV zone, this POM appears to be readily incorporated, metabolized, and/or deposited to bed sediments. Despite representing

Towards an integrated global framework to assess the impacts of land use and management change on soil carbon: current capability and future vision - Pete Smith; Christian A. Davies; Stephen Ogle; Giuliana Zanchi; Jessica Bellarby; Neil Bird; Robert M. Boddey; Niall P. McNamara; David Powlson; Annette Cowie; Meine van Noordwijk; Sarah C. Davis; et al. (Global Change Biology, 2012)
I ntergovernmental P anel on C limate C hange ( IPCC ) T ier 1 methodologies commonly underpin project‐scale carbon accounting for changes in land use and management and are used in frameworks for L ife C ycle A ssessment and carbon footprinting of food and energy crops. These methodologies were intended for use at large spatial scales. This can introduce error in predictions at finer spatial scales. There is an urgent need for development and implementation of higher tier methodologies that can be applied at fine spatial scales (e.g. farm/project/plantation) for food and bioenergy crop greenhouse gas (GHG) accounting to facilitate decision making in the land‐based sectors. Higher tier methods have been defined by IPCC and must be well evaluated and operate across a range of domains (e.g. climate region, soil type, crop type, topography), and must account for land use transitions and management changes being implemented. Furthermore, the data required to calibrate and drive the models used at higher tiers need to be available and applicable at fine spatial resolution, covering the meteorological, soil, cropping system and management domains, with quantified uncertainties. Testing the reliability of the models will require data either from sites with repeated measurements or from chronosequences. We review current global capability for estimating changes in soil carbon at fine spatial scales and present a vision for a framework capable of quantifying land use change and management impacts on soil carbon, which could be used for addressing issues such as bioenergy and biofuel sustainability, food security, forest protection, and direct/indirect impacts of land use change. The aim of this framework is to provide a globally accepted standard of carbon measurement and modelling appropriate for GHG accounting that could be applied at project to national scales (allowing outputs to be scaled up to a country level), to address the impacts of land use and land management change on soil carbon.

Pharmacokinetic Evaluation of Intranasally Administered Vinyl Polymer-Coated Lorazepam Microparticles in Rabbits - Yanjun Zhao; Marc B. Brown; Rajeshree H. Khengar; Matthew J. Traynor; Pedro Barata; Stuart A. Jones (The AAPS Journal, 2012)

Genetic variation among endangered Irish red grouse (Lagopus lagopus hibernicus) populations: implications for conservation and management - Barry J. McMahon; Magnus P. Johansson; Stuart B. Piertney; Kieran Buckley; Jacob Höglund (Conservation Genetics, 2012)

Altered Lung Motion is a Sensitive Indicator of Regional Lung Disease - Andreas Fouras; Beth J. Allison; Marcus J. Kitchen; Stephen Dubsky; Jayne Nguyen; Kerry Hourigan; Karen K. W. Siu; Rob A. Lewis; Megan J. Wallace; Stuart B. Hooper (Annals of Biomedical Engineering, 2012)

An Economic Evaluation of a Small-Scale Timber Harvesting Operation in Western Maryland, USA - Stuart A. Moss; Daniel B. Hedderick (Small-scale Forestry, 2012)

Artificial gravity training reduces bed rest-induced cardiovascular deconditioning - Michael B. Stenger; Joyce M. Evans; Charles F. Knapp; Stuart M. C. Lee; Tiffany R. Phillips; Sondra A. Perez; Alan D. Moore; William H. Paloski; Steven H. Platts (European Journal of Applied Physiology, 2012)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Phytotoxicity of Antofine from Invasive Swallow-Worts - Donna M. Gibson; Stuart B. Krasnoff; Jeromy Biazzo; Lindsey Milbrath (Journal of Chemical Ecology, 2011)

Survey and management of mussel Mytilus species in Scotland - Patricia Joanna Dias; Stuart B. Piertney; Mike Snow; Ian M. Davies (Hydrobiologia, 2011)

Fine-scale genetic structure of bottlenose dolphins, Tursiops truncatus, in Atlantic coastal waters of the Iberian Peninsula - Ruth Fernández; M. Begoña Santos; Graham J. Pierce; Ángela Llavona; Alfredo López; Mόnica A. Silva; Marisa Ferreira; Manuel Carrillo; Pablo Cermeño; Santiago Lens; Stuart B. Piertney (Hydrobiologia, 2011)

Crops that feed the world 4. Barley: a resilient crop? Strengths and weaknesses in the context of food security - Adrian Clive Newton; Andrew J. Flavell; Timothy S. George; Philip Leat; Barry Mullholland; Luke Ramsay; Cesar Revoredo-Giha; Joanne Russell; Brian J. Steffenson; J. Stuart Swanston; William T. B. Thomas; Robbie Waugh; et al. (Food Security, 2011)

A new dawn for industrial photosynthesis - Dan E. Robertson; Stuart A. Jacobson; Frederick Morgan; David Berry; George M. Church; Noubar B. Afeyan (Photosynthesis Research, 2011)

Earth stewardship: a strategy for social–ecological transformation to reverse planetary degradation - F. Stuart Chapin; Steward T. A. Pickett; Mary E. Power; Robert B. Jackson; David M. Carter; Clifford Duke (Journal of Environmental Studies and Sciences, 2011)

Frontiers in host–parasite ecology and evolution - STEVE PATERSON; STUART B. PIERTNEY (Molecular Ecology, 2011)

Proposal for a revised taxonomy of the family Filoviridae: classification, names of taxa and viruses, and virus abbreviations - Jens H. Kuhn; Stephan Becker; Hideki Ebihara; Thomas W. Geisbert; Karl M. Johnson; Yoshihiro Kawaoka; W. Ian Lipkin; Ana I. Negredo; Sergey V. Netesov; Stuart T. Nichol; Gustavo Palacios; Clarence J. Peters; et al. (Archives of Virology, 2010)

Functional traits and the growth–mortality trade‐off in tropical trees - S. Joseph Wright; Kaoru Kitajima; Nathan J. B. Kraft; Peter B. Reich; Ian J. Wright; Daniel E. Bunker; Richard Condit; James W. Dalling; Stuart J. Davies; Sandra Díaz; Bettina M. J. Engelbrecht; Kyle E. Harms; et al. (Ecology, 2010)
A trade‐off between growth and mortality rates characterizes tree species in closed canopy forests. This trade‐off is maintained by inherent differences among species and spatial variation in light availability caused by canopy‐opening disturbances. We evaluated conditions under which the trade‐off is expressed and relationships with four key functional traits for 103 tree species from Barro Colorado Island, Panama. The trade‐off is strongest for saplings for growth rates of the fastest growing individuals and mortality rates of the slowest growing individuals ( r 2 = 0.69), intermediate for saplings for average growth rates and overall mortality rates ( r 2 = 0.46), and much weaker for large trees ( r 2 ≤ 0.10). This parallels likely levels of spatial variation in light availability, which is greatest for fast‐ vs. slow‐growing saplings and least for large trees with foliage in the forest canopy. Inherent attributes of species contributing to the trade‐off include abilities to disperse, acquire resources, grow rapidly, and tolerate shade and other stresses. There is growing interest in the possibility that functional traits might provide insight into such ecological differences and a growing consensus that seed mass (SM), leaf mass per area (LMA), wood density (WD), and maximum height ( H max ) are key traits among forest trees. Seed mass, LMA, WD, and H max are predicted to be small for light‐demanding species with rapid growth and mortality and large for shade‐tolerant species with slow growth and mortality. Six of these trait–demographic rate predictions were realized for saplings; however, with the exception of WD, the relationships were weak ( r 2 r 2 80% of the explained variation and, after WD was included, LMA and H max made insignificant contributions. Virtually the full range of values of SM, LMA, and H max occurred at all positions on the growth–mortality trade‐off. Although WD provides a promising start, a successful trait‐based ecology of tropical forest trees will require consideration of additional traits.

Wetland‐driven shifts in suspended particulate organic matter composition of the Hudson River estuary, New York - Glendon B. Hunsinger; Siddhartha Mitra; Stuart E. G. Findlay; David T. Fischer (Limnology and Oceanography, 2010)
Elemental carbon and nitrogen, stable isotopes, and lignin phenols were quantified for suspended particulate material exchanging between Tivoli Bays wetlands and the main stem of the freshwater‐tidal Hudson River estuary (HRE) across a tidal cycle, seasonally in 2006 and monthly in 2007 during the ice‐free portion of the year. Temporal shifts in organic matter (OM) composition ranged from 33.1 to 247.6 mg g −1 particulate organic carbon (POC), ‐34.7‰ to ‐27.2‰ stable carbon isotopic signature of POC (δ 13 C POC ), ‐3.6‰ to 13.6‰ nitrogen isotopic signature of particulate nitrogen (δ 15 N PN ), and 0.8 to 25.0 mg per 100 mg OC lignin phenols. From May to August, the wetlands transferred abundant (up to 247.6 mg g −1 ), chemically distinctive (δ 13 C POC as depleted as ‐34.7‰) particulate OM to the HRE, particularly Tivoli South Bay. We estimated a net export of > 60 Mg km −2 yr −1 POC from Tivoli Bays into the HRE. Mixing model iterations indicated that planktonic OM was the dominant source (50% to 86%) during summertime, while contributions from allochthonous and planktonic OM during other seasons were roughly equivalent (~ 38%). Taken together, both geochemical data and mixing modeling underscore the function and value of HRE tidal wetlands as major generators of compositionally unique and labile POC for the estuarine carbon budget. In a broader context, lateral aquatic connections with tidal wetlands at seasonal or localized scales may overshadow internal or upland influences on OM composition, production, and processing in estuaries; a latent but key consideration when deciphering temporal and longitudinal trends.

Characterising functionally important and ecologically meaningful genetic diversity using a candidate gene approach - Stuart B. Piertney; Lucy M. I. Webster (Genetica, 2010)

Response of benthic macroinvertebrate communities to highway construction in an Appalachian watershed - Lara B. Hedrick; Stuart A. Welsh; James T. Anderson; Lian-Shin Lin; Yushun Chen; Xinchao Wei (Hydrobiologia, 2010)

Ecological, morphological and genetic divergence of sympatric North Atlantic killer whale populations - ANDREW D. FOOTE; JASON NEWTON; STUART B. PIERTNEY; ESKE WILLERSLEV; M. THOMAS P. GILBERT (Molecular Ecology, 2009)
Ecological divergence has a central role in speciation and is therefore an important source of biodiversity. Studying the micro‐evolutionary processes of ecological diversification at its early stages provides an opportunity for investigating the causative mechanisms and ecological conditions promoting divergence. Here we use morphological traits, nitrogen stable isotope ratios and tooth wear to characterize two disparate types of North Atlantic killer whale. We find a highly specialist type, which reaches up to 8.5 m in length and a generalist type which reaches up to 6.6 m in length. There is a single fixed genetic difference in the mtDNA control region between these types, indicating integrity of groupings and a shallow divergence. Phylogenetic analysis indicates this divergence is independent of similar ecological divergences in the Pacific and Antarctic. Niche‐width in the generalist type is more strongly influenced by between‐individual variation rather than within‐individual variation in the composition of the diet. This first step to divergent specialization on different ecological resources provides a rare example of the ecological conditions at the early stages of adaptive radiation.

Soil drying and nitrogen availability modulate carbon and water exchange over a range of annual precipitation totals and grassland vegetation types - SAMUEL B. St. CLAIR; ERIKA A. SUDDERTH; MARC L. FISCHER; MARGARET S. TORN; STEPHANIE A. STUART; ROHIT SALVE; DENNIS L. EGGETT; DAVID D. ACKERLY (Global Change Biology, 2009)
Increased intensity in precipitation events and longer periods of water deficit are predicted as a general trend under future climate scenarios with potentially large effects on terrestrial ecosystem function. The primary objective of this study was to understand how variation in the intensity of precipitation inputs followed by intermittent soil drying events influence leaf and ecosystem carbon dioxide (CO 2 ) and water exchange in a California annual grassland mesocosm experiment. We further examined how nitrogen (N) availability, and differences in plant community composition (grass‐forb combinations) affected gas exchange responses to the precipitation treatments. Net ecosystem CO 2 exchange (NEE) and evapotranspiration (ET) increased significantly with greater precipitation and were positively correlated with soil moisture. A repeated 10‐day soil drying period, following 11 days of watering, strongly depressed NEE over a range of annual precipitation totals (297, 657 and 987 mm), and plant community types. Ecosystem dark respiration ( R e ) and leaf level photosynthesis ( A max ) showed greater sensitivity to periods of soil drying in the low precipitation plots (297 mm). N additions significantly increased NEE and R e , particularly as water availability was increased. Across the range of precipitation totals and plant community types, intermittent periods of soil moisture deficit and native soil N availability constrained leaf and ecosystem level CO 2 exchange, while the influence on water vapor exchange was less pronounced.

Herbivore metabolism and stoichiometry each constrain herbivory at different organizational scales across ecosystems - Helmut Hillebrand; Elizabeth T. Borer; Matthew E. S. Bracken; Bradley J. Cardinale; Just Cebrian; Elsa E. Cleland; James J. Elser; Daniel S. Gruner; W. Stanley Harpole; Jacqueline T. Ngai; Stuart Sandin; Eric W. Seabloom; et al. (Ecology Letters, 2009)
Plant‐herbivore interactions mediate the trophic structure of ecosystems. We use a comprehensive data set extracted from the literature to test the relative explanatory power of two contrasting bodies of ecological theory, the metabolic theory of ecology (MTE) and ecological stoichiometry (ES), for per‐capita and population‐level rates of herbivory across ecosystems. We found that ambient temperature and herbivore body size (MTE) as well as stoichiometric mismatch (ES) both constrained herbivory, but at different scales of biological organization. Herbivore body size, which varied over 11 orders of magnitude, was the primary factor explaining variation in per‐capita rates of herbivory. Stoichiometric mismatch explained more variation in population‐level herbivory rates and also in per‐capita rates when we examined data from within functionally similar trophic groups (e.g. zooplankton). Thus, predictions from metabolic and stoichiometric theories offer complementary explanations for patterns of herbivory that operate at different scales of biological organization.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Landscape barriers reduce gene flow in an invasive carnivore: geographical and local genetic structure of American mink in Scotland - ANDRZEJ ZALEWSKI; STUART B. PIERTNEY; HANNA ZALEWSKA; XAVIER LAMBIN (Molecular Ecology, 2009)
To be effective, management programmes geared towards halting or reversing the spread of invasive species must focus on defined and defensible areas. This requires knowledge of the dispersal of non‐native species targeted for control to better understand invasion and recolonisation scenarios. We investigated the genetic structure of invasive American mink ( Neovison vison ) in Scotland, and incorporated landscape genetic approaches to examine resultant patterns in relation to geographical features that may influence dispersal. Populations of mink sampled from 10 sites in two regions (Argyll and Northeast Scotland) show a distinct genetic structure. First, the majority of pairwise population comparisons yielded F ST values that were significantly greater than zero. Second, amova revealed that most of the genetic variance was attributable to differences among regions. Assignment tests placed 89 or more of individuals into their sampled region. Bayesian clustering methods grouped samples into two clusters according to their region of origin. Wombling approach identified the Cairngorms Mountains as a major impediment to gene flow between the regions. Mantel pairwise correlations between genetic and geographical distances estimated as least‐cost distance assuming a linear increase in the cost of movement with increasing elevation were higher than Euclidean distances or distance along waterways. Spatial autocorrelation analyses revealed stronger spatial structuring for females than for males. These results suggest that gene flow by American mink is restricted by landscape features (mountain ranges) and that eradication attempt should in the first instance break down the connectivity between management units separated by mountains.

Spatio‐temporal variation in the strength and mode of selection acting on major histocompatibility complex diversity in water vole ( Arvicola terrestris ) metapopulations - MATTHEW K. OLIVER; XAVIER LAMBIN; THOMAS CORNULIER; STUART B. PIERTNEY (Molecular Ecology, 2009)
Patterns of spatio‐temporal genetic variation at a class II major histocompatibility complex (MHC) locus and multiple microsatellite loci were analysed within and between three water vole metapopulations in Scotland, UK. Comparisons of MHC and microsatellite spatial genetic differentiation, based on standardised tests between two demographically asynchronous zones within a metapopulation, suggested that spatial MHC variation was affected by balancing selection, directional selection and random genetic drift, but that the relative effects of these microevolutionary forces vary temporally. At the metapopulation level, between‐year differentiation for MHC loci was significantly correlated with that of microsatellites, signifying that neutral factors such as migration and drift were primarily responsible for overall temporal genetic change at the metapopulation scale. Between metapopulations, patterns of genetic differentiation implied that, at large spatial scales, MHC variation was primarily affected by directional selection and drift. Levels of MHC heterozygosity in excess of Hardy–Weinberg expectations were consistent with overdominant balancing selection operating on MHC variation within metapopulations. However, this effect was not constant among all samples, indicating temporal variation in the strength of selection relative to other factors. The results highlight the benefit of contrasting variation at MHC with neutral markers to separate the effects of stochastic and deterministic microevolutionary forces, and add to a growing body of evidence showing that the mode and relative strength of selection acting on MHC diversity varies both spatially and temporally.

Manipulation of Corticosteroid Release from a Transiently Supersaturated Topical Metered Dose Aerosol Using A Residual Miscible Co-Solvent - Monica L. Reid; Marc B. Brown; Stuart A. Jones (Pharmaceutical Research, 2008)

Replication of association between ELAVL4 and Parkinson disease: the GenePD study - Anita L. DeStefano; Jeanne Latourelle; Mark F. Lew; Oksana Suchowersky; Christine Klein; Lawrence I. Golbe; Margery H. Mark; John H. Growdon; G. Fredrick Wooten; Ray Watts; Mark Guttman; Brad A. Racette; et al. (Human Genetics, 2008)

Employment of 16S rDNA gene sequencing techniques for improved identification of difficult-to-identify bacterial veterinary pathogens - John E. Moore; Yasunori Maeda; Jiru Xu; B. Cherie Millar; Peter H. Herold; V. M. J. Browne-Lauwers; Colin E. Goldsmith; Anne Loughrey; Paul J. Rooney; J. Stuart Elborn; Motoo Matsuda (World Journal of Microbiology and Biotechnology, 2008)

Spatial distribution of mitochondrial and microsatellite DNA variation in Daubenton's bat within Scotland - THONGCHAI NGAMPRASERTWONG; IAIN J. MACKIE; PAUL A. RACEY; STUART B. PIERTNEY (Molecular Ecology, 2008)
Daubenton's bat ( Myotis daubentonii ) is a known reservoir for European bat lyssavirus type 2 (EBLV‐2). An appreciation of the potential for epidemiological spread and disease risk requires an understanding of the dispersal of the primary host, and any large‐scale geographical barriers that may impede gene flow. The spatial pattern of microsatellite and mitochondrial DNA variation was examined to infer patterns of dispersal of bats among 35 populations across Scotland. DNA sequence variation at the mitochondrial control region and ND1 genes revealed two distinct phylogeographical clades, with generally nonoverlapping geographical distributions except for a small number of populations where both matrilines were found in sympatry. Such discontinuity suggests that Scotland was recolonised twice following the retreat of the Pleistocene ice sheet with little subsequent matrilineal introgression. However, eight microsatellite loci showed low levels of genetic divergence among populations, even between populations from the two distinct mitochondrial DNA clades. An overall, macrogeographical genetic isolation‐by‐distance pattern was observed, with high levels of gene flow among local populations. Apparently contrasting patterns of mitochondrial and microsatellite divergence at different scales could be explained by sex‐specific differences in gene flow at large scales.

Lock gates improve passage of small‐bodied fish and crustaceans in a low gradient vertical‐slot fishway - I. G. STUART; L. J. BAUMGARTNER; B. P. ZAMPATTI (Fisheries Management and Ecology, 2008)
A modified ‘lock’ mode of operation was trialled within a low‐slope (3.1%) vertical‐slot fishway to improve passage of small‐bodied ( 50 mm long) did not ascend during the study. Considerable experimental work is required at other sites and at higher fishway slopes before widespread retro‐fitting of lock gates. Nevertheless, these results highlight new options for potentially improving the ecological performance of existing pool‐type fishways and new facilities.

Temporal changes in kin structure through a population cycle in a territorial bird, the red grouse Lagopus lagopus scoticus - STUART B. PIERTNEY; XAVIER LAMBIN; ANDREW D. C. MACCOLL; KERRY LOCK; PHILIP J. BACON; JOHN F. DALLAS; FIONA LECKIE; FRANCOIS MOUGEOT; PAUL A. RACEY; STEVE REDPATH; ROBERT MOSS (Molecular Ecology, 2008)
Populations of red grouse ( Lagopus lagopus scoticus ) undergo regular multiannual cycles in abundance. The ‘kinship hypothesis’ posits that such cycles are caused by changes in kin structure among territorial males producing delayed density‐dependent changes in aggressiveness, which in turn influence recruitment and regulate density. The kinship hypothesis makes several specific predictions about the levels of kinship, aggressiveness and recruitment through a population cycle: (i) kin structure will build up during the increase phase of a cycle, but break down prior to peak density; (ii) kin structure influences aggressiveness, such that there will be a negative relationship between kinship and aggressiveness over the years; (iii) as aggressiveness regulates recruitment and density, there will be a negative relationship between aggressiveness in one year and both recruitment and density in the next; (iv) as kin structure influences recruitment via an affect on aggressiveness, there will be a positive relationship between kinship in one year and recruitment the next. Here we test these predictions through the course of an 8‐year cycle in a natural population of red grouse in northeast Scotland, using microsatellite DNA markers to resolve changing patterns of kin structure, and supra‐orbital comb height of grouse as an index of aggressiveness. Both kin structure and aggressiveness were dynamic through the course of the cycle, and changing patterns were entirely consistent with the expectations of the kinship hypothesis. Results are discussed in relation to potential drivers of population regulation and implications of dynamic kin structure for population genetics.

Determining diel variation in fish assemblages downstream of three weirs in a regulated lowland river - L. J. Baumgartner; I. G. Stuart; B. P. Zampatti (Journal of Fish Biology, 2008)
The diel variation in boat electrofishing catches was investigated on the lower Murray River (south‐eastern Australia), downstream of three low‐level weirs. Fish assemblage composition did not differ among three sites, but differed substantially between day and night. Significantly more small‐bodied species ( e.g. Australian smelt Retropinna semoni , flyspecked hardyhead Craterocephalus stercusmuscarum , bony herring Nematalosa erebi and Murray rainbowfish Melanotaenia fluviatilis ) and some large‐bodied predators ( e.g. golden perch Macquaria ambigua ) were caught during daytime samples. Significantly more flatheaded gudgeon Phylipnodon grandiceps , carp gudgeon Hypseleotris spp. and perch Perca fluviatilis were collected at night. The size composition of the fish assemblage also changed over the diel cycle. Significantly smaller goldfish Carassius auratus , flyspecked hardyhead, bony herring and Australian smelt were sampled during the day, while generally smaller individuals of golden perch and the common carp Cyprinus carpio were caught at night. These findings suggest that sampling during both day and night is required to adequately characterize riverine fish assemblages in the context of fish migration studies.

Effect of carbohydrates on the production of thaxtomin A by Streptomyces acidiscabies - Michael J. Wach; Stuart B. Krasnoff; Rosemary Loria; Donna M. Gibson (Archives of Microbiology, 2007)

Hypertrophy with unilateral resistance exercise occurs without increases in endogenous anabolic hormone concentration - Sarah B. Wilkinson; Mark A. Tarnopolsky; Emily J. Grant; Caroline E. Correia; Stuart M. Phillips (European Journal of Applied Physiology, 2006)

A Parenteral Econazole Formulation Using a Novel Micelle-to-Liposome Transfer Method: In Vitro Characterization and Tumor Growth Delay in a Breast Cancer Xenograft Model - Sebastian Cogswell; Stuart Berger; Dawn Waterhouse; Marcel B. Bally; Ellen K. Wasan (Pharmaceutical Research, 2006)

A Parenteral Econazole Formulation Using a Novel Micelle-to-Liposome Transfer Method: In Vitro Characterization and Tumor Growth Delay in a Breast Cancer Xenograft Model - Sebastian Cogswell; Stuart Berger; Dawn Waterhouse; Marcel B. Bally; Ellen K. Wasan (Pharmaceutical Research, 2006)

Facial Skin Surface Temperature Changes During a “Concealed Information” Test - Dean A. Pollina; Andrew B. Dollins; Stuart M. Senter; Troy E. Brown; Ioannis Pavlidis; James A. Levine; Andrew H. Ryan (Annals of Biomedical Engineering, 2006)

Isolation and characterization of a MHC class II DRB locus in the European water vole (Arvicola terrestris) - Matthew K. Oliver; Stuart B. Piertney (Immunogenetics, 2006)

Determinants of Preferences for Genetic Counselling in Jewish Women - Carmel Apicella; Stuart J. Peacock; Lesley Andrews; Katherine Tucker; Agnes Bankier; Mary B. Daly; John L. Hopper (Familial Cancer, 2006)

Acute meningoencephalitis caused by adenovirus serotype 26 - Erik R Dubberke; Benjamin Tu; Dennis J Rivet; Gregory A Storch; Anucha Apisarnthanarak; Robert E Schmidt; Stuart Weiss; Louis B Polish (Journal of NeuroVirology, 2006)

Genetic Typing of Classical Swine Fever Viruses from Lao PDR by Analysis of the 5′ Non-Coding Region - Stuart D. Blacksell; Syseng Khounsy; David B. Boyle; Laurence J. Gleeson; Harvey A. Westbury; John S. Mackenzie (Virus Genes, 2005)

Evidence and Implications of Recent Climate Change in Northern Alaska and Other Arctic Regions - Larry D. Hinzman; Neil D. Bettez; W. Robert Bolton; F. Stuart Chapin; Mark B. Dyurgerov; Chris L. Fastie; Brad Griffith; Robert D. Hollister; Allen Hope; Henry P. Huntington; Anne M. Jensen; Gensuo J. Jia; et al. (Climatic Change, 2005)

Measurement and nature of firing rate adaptation in turtle spinal neurons - R. B. Gorman; J. C. McDonagh; T. G. Hornby; R. M. Reinking; D. G. Stuart (Journal of Comparative Physiology A, 2005)

Phylogeographic structure and postglacial evolutionary history of water voles ( Arvicola terrestris ) in the United Kingdom - STUART B. PIERTNEY; WENDY A. STEWART; XAVIER LAMBIN; SANDRA TELFER; JON AARS; JOHN F. DALLAS (Molecular Ecology, 2005)
The phylogeographic pattern of mitochondrial DNA variation in water voles ( Arvicola terrestris ) from 57 localities across the United Kingdom and representative samples from Spain, France, Switzerland and Finland was determined from sequence variation in the central portion of the control region. Twenty‐seven different haplotypes were resolved which formed two distinct phylogenetic clades. This major division separated haplotypes found in Scotland from those found in England and Wales. Nested clade analysis of haplotypes indicated that such a division was a consequence of allopatric fragmentation. The haplotypes found in Switzerland, France and Spain clustered with Scottish haplotypes, whereas the haplotype from Finland clustered with the English/Welsh haplotypes. These patterns indicate that contemporary Scottish populations are derived from an Iberian glacial refugium, whereas English and Welsh populations are derived from an eastern European refugium. As such, the postglacial recolonization of the United Kingdom must have involved two colonization events, either in different localities with no subsequent contact, or as two waves separated over time, with the second wave of colonizers displacing the first. An analysis of molecular variance ( amova ) identified significant population genetic divergence within both the major clades, indicative of restricted gene flow and regional population isolation. The implications of both phylogeographical and population genetic structure are discussed in context with the conservation of water voles in Britain.

Control of Tamarix in the Western United States: Implications for Water Salvage, Wildlife Use, and Riparian Restoration - Patrick B. Shafroth; James R. Cleverly; Tom L. Dudley; John P. Taylor; Charles VAN Riper; Edwin P. Weeks; James N. Stuart (Environmental Management, 2005)

Atypical size selection of captive school prawns, Metapenaeus macleayi , by three recreational fishing gears in south‐eastern Australia - Matt K. Broadhurst; Russell B. Millar; Damian J. Young; Michael E. L. Wooden; Stuart Rowland (New Zealand Journal of Marine and Freshwater Research, 2004)
Three manipulative experiments were done to estimate the selectivity of conventional and new sizes and configurations of mesh for school prawns, Metapenaeus macleayi , in three south‐eastern Australian recreational fishing gears (haul, push, and scoop nets). The treatment meshes examined were: (1) conventional‐sized, diamond‐shaped mesh used in all gears (20 mm in scoop nets and 30 mm in push and haul nets); (2) 30 mm in scoop nets; and (3) 40‐mm diamond‐ and (4) 23‐mm square‐shaped mesh in all gears. In all experiments, known quantities of school prawns (6–24 mm carapace length (CL)) were placed in purpose‐built enclosures, monitored to ensure no experimental‐induced stress (as measured by changes in L‐lactate in their haemolymph) and the replicate treatments of the various gear configurations deployed. Escapees from the various treatment nets were collected from the enclosures using fine‐meshed nets. Logistic selection curves were derived for all treatment nets and specific comparisons made within and among gears. All nets had 50% retention lengths (L 50 ) comparable to other penaeid‐catching gears with similar mesh sizes, but most had selection ranges (SRs) that were atypically inflated. The large SRs were attributed to a combination of factors that included the mesh geometry and towing speed of the gears and the behaviour of school prawns. The 20‐mm scoop net had the smallest selection parameters, retaining >99% of individuals larger than 13 mm CL. Mesh size in this gear would need to be increased to at least 30 mm to allow some maturing prawns (>18 mm CL) to escape.

Three-dimensional Structure of an Old-growth Pseudotsuga-Tsuga Canopy and Its Implications for Radiation Balance, Microclimate, and Gas Exchange - Geoffrey G. Parker; Mark E. Harmon; Michael A. Lefsky; Jiquan Chen; Robert Van Pelt; Stuart B. Weis; Sean C. Thomas; William E. Winner; David C. Shaw; Jerry F. Frankling (Ecosystems, 2004)

Disconnects in Evaluating the Relative Effectiveness of Conservation Strategies - Kathryn A. Saterson; Norman L. Christensen; Robert B. Jackson; Randall A. Kramer; Stuart L. Pimm; Martin D. Smith; Jonathan B. Wiener (Conservation Biology, 2004)

Delineation of complex chromosomal rearrangements: evidence for increased complexity - Caroline Astbury; Laurie A. Christ; David J. Aughton; Suzanne B. Cassidy; Atsuko Fujimoto; Beth A. Pletcher; Irwin A. Schafer; Stuart Schwartz (Human Genetics, 2004)

Effects of water loss on primary production: A landscape-scale model - Emily H. Stanley; Stuart G. Fisher; Jeremy B. Jones, Jr. (Aquatic Sciences, 2004)

Simultaneous vs. Sequential Analysis for Population PK/PD Data II: Robustness of Methods - Liping Zhang; Stuart L. Beal; Lewis B. Sheiner (Journal of Pharmacokinetics and Pharmacodynamics, 2003)

Simultaneous vs. Sequential Analysis for Population PK/PD Data I: Best-Case Performance - Liping Zhang; Stuart L. Beal; Lewis B. Sheiner (Journal of Pharmacokinetics and Pharmacodynamics, 2003)

Induction of Hypericins and Hyperforins in Hypericum perforatum in Response to Damage by Herbivores - Tara M. Sirvent; Stuart B. Krasnoff; Donna M. Gibson (Journal of Chemical Ecology, 2003)

Simplified seismic fatigue evaluation for rigid steel connections - Ayman A. Shama; John B. Mander; Stuart S. Chen (Earthquake Engineering and Engineering Vibration, 2003)

Similar estimates of population genetic composition and sex ratio derived from carcasses and faeces of Eurasian otter Lutra lutra - John F. Dallas; Karen E. Coxon; Tim Sykes; Paul R. F. Chanin; Freda Marshall; David N. Carss; Philip J. Bacon; Stuart B. Piertney; Paul A. Racey (Molecular Ecology, 2003)
Collecting faeces is viewed as a potentially efficient way to sample elusive animals. Nonetheless, any biases in estimates of population composition associated with such sampling remain uncharacterized. The goal of this study was to compare estimates of genetic composition and sex ratio derived from Eurasian otter Lutra lutra spraints (faeces) with estimates derived from carcasses. Twenty per cent of 426 wild‐collected spraints from SW England yielded composite genotypes for 7–9 microsatellites and the SRY gene. The expected number of incorrect spraint genotypes was negligible, given the proportions of allele dropout and false allele detection estimated using paired blood and spraint samples of three captive otters. Fifty‐two different spraint genotypes were detected and compared with genotypes of 70 otter carcasses from the same area. Carcass and spraint genotypes did not differ significantly in mean number of alleles, mean unbiased heterozygosity or sex ratio, although statistical power to detect all but large differences in sex ratio was low. The genetic compositions of carcass and spraint genotypes were very similar according to confidence intervals of θ and two methods for assigning composite genotypes to groups. A distinct group of approximately 11 carcass and spraint genotypes was detected using the latter methods. The results suggest that spraints can yield unbiased estimates of population genetic composition and sex ratio.

Spatially restricted gene flow and reduced microsatellite polymorphism in the Eurasian otter Lutra lutra in Britain - John F. Dallas; Freda Marshall; Stuart B. Piertney; Philip J. Bacon; Paul A. Racey (Conservation Genetics, 2002)

Sources of Nitrogen to the Riparian Zone of a Desert Stream: Implications for Riparian Vegetation and Nitrogen Retention - John D. Schade; Eugenia Marti; Jill R. Welter; Stuart G. Fisher; Nancy B. Grimm (Ecosystems, 2002)

Pleurochrysis pseudoroscoffensis (Prymnesiophyceae) blooms on the surface of the Salton Sea, California - Kristen M. Reifel; Michael P. McCoy; Mary Ann Tiffany; Tonie E. Rocke; Charles C. Trees; Steven B. Barlow; D. John Faulkner; Stuart H. Hurlbert (Hydrobiologia, 2001)

Chattonella marina (Raphidophyceae), a potentially toxic alga in the Salton Sea, California - Mary A. Tiffany; Steven B. Barlow; Victoria E. Matey; Stuart H. Hurlbert (Hydrobiologia, 2001)

Primary productivity of planet earth: biological determinants and physical constraints in terrestrial and aquatic habitats - Richard J. Geider; Evan H. Delucia; Paul G. Falkowski; Adrien C. Finzi; J. Philip Grime; John Grace; Todd M. Kana; Julie La Roche; Stephen P. Long; Bruce A. Osborne; Trevor Platt; I. Colin Prentice; et al. (Global Change Biology, 2001)

The Need for Mixed-Effects Modeling with Population Dichotomous Data - Ikuko Yano; Stuart L. Beal; Lewis B. Sheiner (Journal of Pharmacokinetics and Pharmacodynamics, 2001)

Microhardness and Dislocation Identification Studies on Paracetamol Single Crystals - Stuart Finnie; Korlakunte V. R. Prasad; David B. Sheen; John N. Sherwood (Pharmaceutical Research, 2001)

Agonistic behavior in naïve juvenile lobsters depleted of serotonin by 5,7-dihydroxytryptamine - Sarah B. Doernberg; Stuart I. Cromarty; Ralf Heinrich; Barbara S. Beltz; Edward A. Kravitz (Journal of Comparative Physiology A, 2001)

Evaluating Pharmacokinetic/Pharmacodynamic Models Using the Posterior Predictive Check - Yoshitaka Yano; Stuart L. Beal; Lewis B. Sheiner (Journal of Pharmacokinetics and Pharmacodynamics, 2001)

Species‐specific responses of plant communities to altered carbon and nutrient availability - Geeske Joel; F. Stuart Chapin; Nona R. Chiariello; Susan S. Thayer; Christopher B. Field (Global Change Biology, 2001)
Summary In a field microcosm experiment, species‐specific responses of aboveground biomass of two California annual grassland communities to elevated CO 2 and nutrient availability were investigated. One community grows on shallow, nutrient‐poor serpentine‐derived soil whereas the other occurs on deeper, modestly fertile sandstone/greenstone‐derived substrate. In most species, CO 2 effects did not appear until late in the growing season, probably because the elevated CO 2 increased water‐use‐efficiency easing, the onset of the summer drought. Responses of aboveground biomass to elevated CO 2 differed depending on nutrient availability. Similarly, biomass responses to nutrient treatments differed depending on the CO 2 status. For the majority of the species, production increased most under elevated CO 2 with added nutrients (N,P,K, and micro nutrients). Some species were losers under conditions that increased overall community production, including Bromus hordeaceus in the serpentine community (negative biomass response under elevated CO 2 ) and Lotus wrangelianus in both communities (negative biomass response with added nitrogen). Treatment and competitive effects on species‐specific biomass varied in both magnitude and direction, especially in the serpentine community, significantly affecting community structure. Individual resource environments are likely to be affected by neighbouring plants, and these competitive interactions complicate predictions of species' responses to elevated CO 2 .

Fuzzy structure and spatial dynamics of a declining woodland caribou population - James A. Schaefer; Alasdair M. Veitch; Fred H. Harrington; W. Kent Brown; John B. Theberge; Stuart N. Luttich (Oecologia, 2001)

The controls on net ecosystem productivity along an Arctic transect: a model comparison with flux measurements - Mathew Williams; Werner Eugster; Edward B. Rastetter; Joseph P. Mcfadden; F. Stuart Chapin Iii (Global Change Biology, 2000)
Summary Assessments of carbon (C) fluxes in the Arctic require detailed data on both how and why these fluxes vary across the landscape. Such assessments are complicated because tundra vegetation has diverse structure and function at both local and regional scales. To investigate this diversity, the Arctic Flux Study has used the eddy covariance technique to generate ecosystem CO 2 ‐exchange data along a transect in northern Alaska. We use an extant process‐based model of the soil–plant–atmosphere continuum to make independent predictions of gross photosynthesis and foliar respiration at 9 of the sites along the transect, using data on local canopy structure and meteorology. We make two key assumptions: (i) soil respiration is constant throughout the flux measurement period, so that the diurnal cycle in CO 2 exchange is driven by canopy processes only (except at two sites where a soil respiration–temperature relationship was indicated in the data); and (ii) mosses and lichens play an insignificant role in ecosystem C exchange, even though in some locations their live biomass exceeds 300 g m −2 . We found that even with these assumptions the model could explain much of the dynamics of net ecosystem production (NEP) at sites with widely differing vegetation structure and moss/lichen cover. Errors were mostly associated with the predictions of maximum NEP; the likely cause of such discrepancies was (i) a mismatch between vegetation sampled for characterizing the canopy structure and that contained within the footprint of the eddy covariance flux measurements, or (ii) an increase in daytime soil and root respiration. Thus the model results tended to falsify our first assumption but not our second. We also note evidence for an actual reduction in NEP caused by water stress on warm, dry days at some sites. The model–flux comparison also suggests that photosynthesis may be less sensitive to low temperatures than leaf‐level gas‐exchange measurements have indicated.

Sex identification of the Eurasian otter Lutra lutra by PCR typing of spraints - John F. Dallas; David N. Carss; Freda Marshall; Klaus-Peter Koepfli; Hans Kruuk; Philip J. Bacon; Stuart B. Piertney (Conservation Genetics, 2000)

Institutional Reform in Albania: Making Forest-Based Policies Work - Kozma Naka; A. L. Hammett; William B. Stuart (Journal of Forestry, 2000)
In response to such problems as illegal timber harvesting and overgrazing, policymakers in Albania are making efforts to increase the efficiency of the country's forest and pasture administration. Reforms include decentralization, development of infrastructure and human resources, and the introduction of a forestry extension service. The authors explore several options and posit that it is more appropriate to work with existing establishments and build partnerships among stakeholders than to create new organizations.

Isolation and characterization of microsatellite loci in the freshwater gastropod, Biomphalaria glabrata , an intermediate host for Schistosoma mansoni - Catherine S. Jones; Anne E. Lockyer; David Rollinson; Stuart B. Piertney; Leslie R. Noble (Molecular Ecology, 1999)

Cars, Cows, and Checkerspot Butterflies: Nitrogen Deposition and Management of Nutrient‐Poor Grasslands for a Threatened Species - Stuart B. Weiss (Conservation Biology, 1999)
Nutrient‐poor, serpentinitic soils in the San Francisco Bay area sustain a native grassland that supports many rare species, including the Bay checkerspot butterfly ( Euphydryas editha bayensis ). Nitrogen (N) deposition from air pollution threatens biodiversity in these grasslands because N is the primary limiting nutrient for plant growth on serpentinitic soils. I investigated the role of N deposition through surveys of butterfly and plant populations across different grazing regimes, by literature review, and with estimates of N deposition in the region. Several populations of the butterfly in south San Jose crashed following the cessation of cattle grazing. Nearby populations under continued grazing did not suffer similar declines. The immediate cause of the population crashes was rapid invasion by introduced annual grasses that crowded out the larval host plants of the butterfly. Ungrazed serpentinitic grasslands on the San Francisco Peninsula have largely resisted grass invasions for nearly four decades. Several lines of evidence indicate that dry N deposition from smog is responsible for the observed grass invasion. Fertilization experiments have shown that soil N limits grass invasion in serpentinitic soils. Estimated N deposition rates in south San Jose grasslands are 10–15 kg N/ha/year; Peninsula sites have lower deposition, 4–6 kg N/ha/year. Grazing cattle select grasses over forbs, and grazing leads to a net export of N as cattle are removed for slaughter. Although poorly managed cattle grazing can significantly disrupt native ecosystems, in this case moderate, well‐managed grazing is essential for maintaining native biodiversity in the face of invasive species and exogenous inputs of N from nearby urban areas.

GLM versus CCA spatial modeling of plant species distribution - Antoine Guisan; Stuart B. Weiss; Andrew D. Weiss (Plant Ecology, 1999)

Local genetic structure in red grouse ( Lagopus lagopus scoticus ): evidence from microsatellite DNA markers - STUART B. PIERTNEY; ANDREW D. C. MACCOLL; PHILIP J. BACON; JOHN F. DALLAS (Molecular Ecology, 1998)
Allelic variation at seven hypervariable tri‐ and tetranucleotide microsatellite loci was used to determine levels of population differentiation between 14 populations of red grouse ( Lagopus lagopus scoticus ) in northeast Scotland, UK. Despite the potential for long‐distance dispersal in grouse, and a semicontinuous habitat, significant population divergence was observed (mean R ST = 0.153; P P

Vasopressin regulated trafficking of a green fluorescent protein-aquaporin 2 chimera in LLC-PK1 cells - Corinne E. Gustafson; Stuart Levine; Toshiya Katsura; Margaret McLaughlin; Maria Deize Aleixo; B. K. Tamarappoo; A. S. Verkman; D. Brown (Histochemistry and Cell Biology, 1998)

Genotype/phenotype correlation in affected individuals of a family with a deletion of the entire coding sequence of the connexin 32 gene - P. J. Ainsworth; C. F. Bolton; B. C. Murphy; J. A. Stuart; A. F. Hahn (Human Genetics, 1998)

Breath, urine, and blood measurements as biological exposure indices of short-term inhalation exposure to methanol - Stuart A. Batterman; Alfred Franzblau; James B. D'Arcy; Nicholas E. Sargent; Kenneth B. Gross; Richard M. Schreck (International Archives of Occupational and Environmental Health, 1998)

Landscape-Level Phenology of a Threatened Butterfly: A GIS-Based Modeling Approach - Stuart B. Weiss; Andrew D. Weiss (Ecosystems, 1998)

Material Spiraling in Stream Corridors: A Telescoping Ecosystem Model - Stuart G. Fisher; Nancy B. Grimm; Eugènia Martí; Robert M. Holmes; Jeremy B. Jones, Jr. (Ecosystems, 1998)

Twenty-Five Years of the Clean Water Act: How Clean Are Forest Practices? - George G. Ice; Gordon W. Stuart; Jack B. Waide; Lloyd C. Irland; Paul V. Ellefson (Journal of Forestry, 1997)

Identification of an assimilatory nitrate reductase in mutants of Paracoccus denitrificans GB17 deficient in nitrate respiration - Heather J. Sears; Phillip J. Little; D. J. Richardson; B. C. Berks; Stephen Spiro; Stuart J. Ferguson (Archives of Microbiology, 1997)

The expression of redox proteins of denitrification inThiosphaera pantotropha grown with oxygen, nitrate, and nitrous oxide as electron acceptors - James W. B. Moir; David J. Richardson; Stuart J. Ferguson (Archives of Microbiology, 1995)

Integrin-binding peptide in solution inhibits or enhances endothelial cell migration, predictably from cell adhesion - Peng Wu; James B. Hoying; Stuart K. Williams; Barbara A. Kozikowski; Douglas A. Lauffenburger (Annals of Biomedical Engineering, 1994)

Review of literature - E. V. Hardenburg; W. M. Stuart; C. H. Metsger; W. B. Ward (American Journal of Potato Research, 1934)

Notes - E. V. Hardenburg; J. T.; M. B. Chalker; F. M. Harrington; H. C. M; W. P. Kirkwood; A. G. Tolaas; W. Stuart (American Journal of Potato Research, 1930)

Notes - J. T.; E. B. Tussing; WM. Stuart; P. M. Lombard; H. L. Bailey; F. M. H. (American Journal of Potato Research, 1928)

Notes - H. C. Moore; N. J. Thomas; C. W. Metzger; E. R. Bennett; C. W. Hungerford; W M. Stuart; W M. H. Martin; E. B. Tussing; H. H. Zimmerley; H. O. Werner (American Journal of Potato Research, 1928)

Kiwanians sponsor potato club work - P. R. Young; E. V. Hardenburg; B. E. Brown; Paul M. Williams; Daniel Dean; A. G. Waller; H. R. Talmage; H. C. Moore; J. G. Milward; W. Stuart; H. B. Stevens; R. W. Goss; et al. (American Journal of Potato Research, 1925)

Potato notes - J. T. Rosa; C. Tice; A. E. Wilkinson; B. G. Southwick; E. A. Stokdyk; Ray D. Hews; E. L. Newdick; W. Stuart; H. C. Moore; H. O. Werner; J. F. Hockey; C. L. Bailey; et al. (American Journal of Potato Research, 1924)

Notes on recent literature - W. Stuart; W. M. Peacock; W. S. Baird; W. Saxby Blair; R. H. Helmer; W. H. Hicks; W. R. Leslie; B. F. Lutman; H. H. Mann; S. D. Nagpurkar; G. S. Kulkarni; R. S. Kasargode; et al. (American Journal of Potato Research, 1924)